Modified vinyl alcohol polymer, method for producing modified vinyl alcohol polymer, particles, aqueous solution, coating liquid, coated product, molded body, release paper, dispersant, method for producing vinyl polymer, and mixture

A modified vinyl alcohol polymer with a silane coupling agent addresses handling and solubility issues, enhancing performance in coating liquids and dispersants, and improves silicone curability in release papers.

CN116635503BActive Publication Date: 2024-12-17KURARAY CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202180086949.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-07-09
Filing Date
2021-12-22
Publication Date
2024-12-17
Estimated Expiration
2041-12-22

AI Technical Summary

Technical Problem

Existing vinyl alcohol polymers (PVA) face issues with handling properties, water solubility, and cross-linking during drying, leading to decreased effectiveness in applications such as coating liquids and dispersants, and lack sufficient silicone curability and adhesion in release papers.

Method used

A modified vinyl alcohol polymer with a silane coupling agent integrated into its structure, having a specific structural unit and low water-insoluble content, is produced through impregnation and heat-treatment, resulting in improved solubility and adhesion, and used in coating liquids, dispersants, and release papers.

Benefits of technology

The modified PVA exhibits excellent handling properties, enhanced water solubility, and superior silicone curability, reducing particle size and insoluble components, thus improving application performance in coating liquids, dispersants, and release papers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116635503B_ABST
    Figure CN116635503B_ABST
Patent Text Reader

Abstract

A modified vinyl alcohol polymer having a structural unit represented by the following formula (1), wherein the water-insoluble component is 1000 ppm or less. In the formula (1), X, Y and Z are each independently an alkyl group having 1 to 20 carbon atoms, an alkenyl group having 2 to 20 carbon atoms, a phenyl group, a benzyl group, a vinylphenyl group, a haloalkyl group having 1 to 20 carbon atoms, a halophenyl group, an aminoalkyl group having 1 to 20 carbon atoms, a mercaptoalkyl group having 1 to 20 carbon atoms, a ureaalkyl group having 2 to 20 carbon atoms, an isocyanatealkyl group having 2 to 8 carbon atoms, a group having 3 to 20 carbon atoms including an epoxy group, a group having 3 to 20 carbon atoms including an acrylamide group, a group having 4 to 20 carbon atoms including a methacrylamide group, an acetoxy group or -(CH2) n ‑O‑R 1 (R 1 represents an alkyl group having 1 to 20 carbon atoms, and n represents an integer of 0 to 6. #imgabs0#
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a modified vinyl alcohol polymer, a method for producing a modified vinyl alcohol polymer, polymer particles, an aqueous solution, a coating liquid, a coated product, a molded body, a release paper, a dispersant, a method for producing a vinyl polymer, and a mixture. Background Art

[0002] Vinyl alcohol polymers (hereinafter sometimes abbreviated as "PVA") are water-soluble and are used in various applications such as synthetic fiber raw materials, film raw materials, emulsifying and dispersing agents, and adhesives.

[0003] PVA is generally obtained by saponifying a vinyl ester polymer obtained by polymerizing a vinyl ester monomer. It is known that modified PVA having special functions can be obtained by saponifying a modified vinyl ester polymer obtained by copolymerizing a vinyl ester monomer with a monomer having various functional groups.

[0004] On the other hand, various "post-modification" methods have been reported in which a reactant having various functional groups reacts with saponified PVA to introduce a functional group derived from the reactant into PVA. For example, post-modification such as the example of using a dicarboxylic acid as a modifier (Patent Document 1) is a useful technique for manufacturing modified PVA.

[0005] In addition, an anti-fogging composition (Patent Document 2), a resin composition (Patent Document 3), a fiber treating agent (Patent Document 4), and the like in which PVA or a derivative thereof is mixed with a silane coupling agent have been reported.

[0006] In addition, Patent Document 5 discloses a method for obtaining modified PVA by reacting PVA with a specific silane coupling agent.

[0007] However, none of the above-mentioned documents 1 to 5 discloses a modified PVA that has a polymer structure in which a silane coupling agent is introduced into PVA, has better handling properties, and can be applied to a variety of purposes. For example, when a modified PVA with low water solubility is used in a coating liquid, a dispersant for suspension polymerization, etc., it sometimes takes time to fully dissolve it, or the insoluble components cause an undesirable effect. In addition, in patent document 5, the reaction of PVA and a specific silane coupling agent is carried out in an aqueous solution, and the modified PVA is obtained in the form of a solution. From the viewpoints of handling, storage, and transportability, it is expected that this solution-state modified PVA will be improved. In addition, when a solution-state modified PVA is made into particles by drying, etc., there is a tendency for a cross-linking reaction to occur during the drying process, resulting in a decrease in water solubility.

[0008] In addition, PVA is used in the paper field as a paper strength enhancer, a dispersant for fluorescent white pigments, and a binder for inorganic substances (calcium carbonate, clay, silica, etc.). PVA has excellent film-forming properties, so by coating it on paper, it can be given barrier properties against gases and oil resistance.

[0009] Paper coated with PVA is sometimes used as barrier paper. As a representative example of barrier paper, release paper base paper can be cited. Release paper base paper is usually manufactured by coating PVA on the surface of a cellulose substrate. And, a release paper is obtained by forming a release layer (silicone layer) on the surface of the release paper base paper. The PVA in the release paper plays the role of a filler that inhibits the penetration of expensive silicone and platinum into the substrate. Recently, a release paper base paper that can promote the curing of silicone in the release layer or improve the adhesion between the PVA layer and the silicone layer on the basis of this filling property is sought.

[0010] Patent Document 6 describes a release paper base coated with PVA that satisfies specific conditions and has a silyl group. Patent Document 7 describes PVA that has double bonds introduced into the side chains by an acetalization reaction. However, these Documents 6 and 7 do not disclose a coating liquid that has excellent silicone curability and adhesion to a substrate.

[0011] In addition, PVA is also widely used as a dispersant, for example, as a dispersion stabilizer for suspension polymerization and emulsion polymerization of vinyl compounds. In particular, it is useful as a dispersion stabilizer used in suspension polymerization of vinyl chloride.

[0012] The obtained polyvinyl chloride resin (hereinafter sometimes referred to as "PVC resin") has excellent chemical resistance and electrical insulation properties, and also has excellent processability, and can be hard or soft, and is therefore used in a wide range of applications as a material for various molding processes. PVC resin is generally produced on an industrial scale by a suspension polymerization method in which a vinyl chloride monomer is polymerized in an aqueous medium in the presence of a dispersion stabilizer using an oil-soluble polymerization initiator.

[0013] As a dispersion stabilizer used in the polymerization of vinyl chloride, PVA is often used, and for the purpose of improving the stability of vinyl chloride during polymerization (polymerization stability), the use of PVA having an olefinic double bond has been proposed (Patent Document 8). However, the above-mentioned Document 8 does not disclose a dispersant containing a modified PVA having a specific structure derived from a silane coupling agent.

[0014] Prior art literature

[0015] Patent Literature

[0016] Patent Document 1: International Publication No. 2007 / 119735

[0017] Patent Document 2: Japanese Patent Application Laid-Open No. 48-47939

[0018] Patent Document 3: Japanese Patent Application Laid-Open No. 2002-275338

[0019] Patent Document 4: Japanese Patent Application Laid-Open No. 6-16738

[0020] Patent Document 5: Japanese Patent Application Laid-Open No. 3-119002

[0021] Patent Document 6: Japanese Patent Application Publication No. 2005-194672

[0022] Patent Document 7: Japanese Patent Application No. 2013-531136

[0023] Patent Document 8: International Publication No. 2019 / 181915 Summary of the invention

[0024] Problems to be solved by the invention

[0025] The purpose of the present application is to provide a modified vinyl alcohol polymer having a polymer structure into which a silane coupling agent is introduced, having excellent handleability, and being useful in various applications; a method for producing the modified vinyl alcohol polymer, particles of the modified vinyl alcohol polymer, and an aqueous solution of the modified vinyl alcohol polymer.

[0026] Another object of the present application is to provide a coating liquid capable of forming a coating layer having excellent silicone curability and adhesion to a substrate; and a coated article, a molded body, and a release paper obtained by applying the coating liquid to a substrate.

[0027] Furthermore, the present application aims to provide a dispersant which can reduce the average particle size of the obtained vinyl polymer, reduce the amount of coarse particles and reduce fish eyes by using it in the production process of the vinyl polymer; a method for producing the vinyl polymer and a mixture.

[0028] Means used to solve problems

[0029] The present invention includes the following disclosures.

[0030] [1] A modified vinyl alcohol polymer having a structural unit represented by the following formula (1) and a water-insoluble component of 1000 ppm or less;

[0031] [Chemistry 1]

[0032]

[0033] [In the formula (1), X, Y and Z are each independently an alkyl group having 1 to 20 carbon atoms, an alkenyl group having 2 to 20 carbon atoms, a phenyl group, a benzyl group, a vinylphenyl group, a haloalkyl group having 1 to 20 carbon atoms, a halophenyl group, an aminoalkyl group having 1 to 20 carbon atoms, a mercaptoalkyl group having 1 to 20 carbon atoms, a ureidoalkyl group having 2 to 20 carbon atoms, an isocyanatealkyl group having 2 to 8 carbon atoms, a group having 3 to 20 carbon atoms including an epoxy group, a group having 3 to 20 carbon atoms including an acrylamide group, a group having 4 to 20 carbon atoms including a methacrylamide group, an acetoxy group or -(CH2) n -OR 1 (R 1 represents a hydrogen atom, an alkali metal atom, an alkaline earth metal atom, an alkyl group having 1 to 20 carbon atoms, an alkenyl group having 2 to 20 carbon atoms, an acryloyl group, a methacryloyl group or a glycidyl group, and n represents an integer of 0 to 6. )

[0034] [2] The modified vinyl alcohol polymer according to [1], wherein the content of the structural unit represented by the formula (1) is 0.01 mol% or more and less than 5 mol%;

[0035] [3] The modified vinyl alcohol polymer according to [1] or [2], wherein the content of the structural unit represented by the above formula (1) is 90 mol% or more relative to all structural units containing silicon atoms;

[0036] [4] A method for producing a modified vinyl alcohol polymer, comprising the step of impregnating a solid vinyl alcohol polymer with a silane coupling agent;

[0037] [5] The method for producing a modified vinyl alcohol polymer according to [4], wherein in the impregnation step, the vinyl alcohol polymer particles are impregnated by spraying the solution containing the silane coupling agent;

[0038] [6] The method for producing a modified vinyl alcohol polymer according to [4] or [5], wherein the silane coupling agent has a structure represented by the following formula (2);

[0039] [Chemistry 2]

[0040]

[0041] [In formula (2), R is an alkyl group having 1 to 8 carbon atoms, an acetyl group or -(CH2) m -OR 2 (R 2represents an alkyl group having 1 to 20 carbon atoms, and m represents an integer of 1 to 6. ). X, Y and Z are each independently an alkyl group having 1 to 20 carbon atoms, an alkenyl group having 2 to 20 carbon atoms, a phenyl group, a benzyl group, a vinylphenyl group, a haloalkyl group having 1 to 20 carbon atoms, a halophenyl group, an aminoalkyl group having 1 to 20 carbon atoms, a mercaptoalkyl group having 1 to 20 carbon atoms, a ureidoalkyl group having 2 to 20 carbon atoms, an isocyanatealkyl group having 2 to 8 carbon atoms, a group having 3 to 20 carbon atoms including an epoxy group, a group having 3 to 20 carbon atoms including an acrylamide group, a group having 4 to 20 carbon atoms including a methacrylamide group, an acetoxy group or -(CH2) n -OR 1 (R 1 represents an alkyl group having 1 to 20 carbon atoms, an alkenyl group having 2 to 20 carbon atoms, an acryloyl group, a methacryloyl group or a glycidyl group, and n represents an integer of 0 to 6. )

[0042] [7] The method for producing a modified vinyl alcohol polymer according to [4], [5] or [6], further comprising: a step of heat-treating the vinyl alcohol polymer impregnated with the silane coupling agent obtained in the impregnation step;

[0043] [8] Particles comprising the modified vinyl alcohol polymer of [1], [2] or [3];

[0044] [9] The particles according to [8], wherein the dispersion degree A of silicon atoms is greater than or equal to 0.2 and less than 1;

[0045]

[10] An aqueous solution comprising the modified vinyl alcohol polymer of [1], [2] or [3];

[0046]

[11] A coating liquid comprising a modified vinyl alcohol polymer having a structural unit represented by the following formula (1);

[0047] [Chemistry 3]

[0048]

[0049] [In the formula (1), X, Y and Z are each independently an alkyl group having 1 to 20 carbon atoms, an alkenyl group having 2 to 20 carbon atoms, a phenyl group, a benzyl group, a vinylphenyl group, a haloalkyl group having 1 to 20 carbon atoms, a halophenyl group, an aminoalkyl group having 1 to 20 carbon atoms, a mercaptoalkyl group having 1 to 20 carbon atoms, a ureidoalkyl group having 2 to 20 carbon atoms, an isocyanatealkyl group having 2 to 8 carbon atoms, a group having 3 to 20 carbon atoms including an epoxy group, a group having 3 to 20 carbon atoms including an acrylamide group, a group having 4 to 20 carbon atoms including a methacrylamide group, an acetoxy group or -(CH2) n -OR 1 (R1 represents a hydrogen atom, an alkali metal atom, an alkaline earth metal atom, an alkyl group having 1 to 20 carbon atoms, an alkenyl group having 2 to 20 carbon atoms, an acryloyl group, a methacryloyl group or a glycidyl group, and n represents an integer of 0 to 6. )

[0050]

[12] The coating liquid according to

[11] , wherein the content of the structural unit represented by the above formula (1) in the above modified vinyl alcohol polymer is 0.01 mol% or more and less than 5 mol%;

[0051]

[13] The coating liquid according to

[11] or

[12] , wherein the content of the structural unit represented by the above formula (1) in the above modified vinyl alcohol polymer is 90 mol% or more relative to the total structural units containing silicon atoms;

[0052]

[14] The coating liquid according to

[11] ,

[12] or

[13] , wherein the viscosity average degree of polymerization of the modified vinyl alcohol polymer is 500 to 5000, and the degree of saponification is 70 mol % to 99.9 mol %;

[0053]

[15] The coating liquid according to any one of

[11] to

[14] , wherein the insoluble content of the modified vinyl alcohol polymer in the coating liquid is 1000 ppm or less;

[0054]

[16] A coated article, which is obtained by coating the coating liquid of any one of

[11] to

[15] on a substrate;

[0055]

[17] A molded article comprising a layer containing a modified vinyl alcohol polymer, wherein the modified vinyl alcohol polymer has a structural unit represented by the following formula (1′);

[0056] [Chemistry 4]

[0057]

[0058] [In the formula (1'), X, Y and Z are each independently an alkyl group having 1 to 20 carbon atoms, an alkenyl group having 2 to 20 carbon atoms, a phenyl group, a benzyl group, a vinylphenyl group, a haloalkyl group having 1 to 20 carbon atoms, a halophenyl group, an aminoalkyl group having 1 to 20 carbon atoms, a mercaptoalkyl group having 1 to 20 carbon atoms, a ureidoalkyl group having 2 to 20 carbon atoms, an isocyanatealkyl group having 2 to 8 carbon atoms, a group having 3 to 20 carbon atoms including an epoxy group, a group having 3 to 20 carbon atoms including an acrylamide group, a group having 4 to 20 carbon atoms including a methacrylamide group, an acetoxy group or -(CH2) n -OR 1 (R 1represents a hydrogen atom, an alkali metal atom, an alkaline earth metal atom, an alkyl group having 1 to 20 carbon atoms, an alkenyl group having 2 to 20 carbon atoms, an acryloyl group, a methacryloyl group, a glycidyl group or a linking bond, and n represents an integer of 0 to 6. )

[0059]

[18] A release paper comprising a substrate, a silicone plugging layer and a release layer, wherein the silicone plugging layer comprises a modified vinyl alcohol polymer having a structural unit represented by the following formula (1');

[0060] [Chemistry 5]

[0061]

[0062] [In the formula (1'), X, Y and Z are each independently an alkyl group having 1 to 20 carbon atoms, an alkenyl group having 2 to 20 carbon atoms, a phenyl group, a benzyl group, a vinylphenyl group, a haloalkyl group having 1 to 20 carbon atoms, a halophenyl group, an aminoalkyl group having 1 to 20 carbon atoms, a mercaptoalkyl group having 1 to 20 carbon atoms, a ureidoalkyl group having 2 to 20 carbon atoms, an isocyanatealkyl group having 2 to 8 carbon atoms, a group having 3 to 20 carbon atoms including an epoxy group, a group having 3 to 20 carbon atoms including an acrylamide group, a group having 4 to 20 carbon atoms including a methacrylamide group, an acetoxy group or -(CH2) n -OR 1 (R 1 represents a hydrogen atom, an alkali metal atom, an alkaline earth metal atom, an alkyl group having 1 to 20 carbon atoms, an alkenyl group having 2 to 20 carbon atoms, an acryloyl group, a methacryloyl group, a glycidyl group or a linking bond, and n represents an integer of 0 to 6. )

[0063]

[19] The release paper according to

[18] , wherein the release layer comprises addition silicone and platinum, and the content of the platinum is 0.001 to 0.05 parts by mass based on 100 parts by mass of the addition silicone.

[0064]

[20] A dispersant comprising a modified vinyl alcohol polymer having a structural unit represented by the following formula (1);

[0065] [Chemistry 6]

[0066]

[0067] [In the formula (1), X, Y and Z are each independently an alkyl group having 1 to 20 carbon atoms, an alkenyl group having 2 to 20 carbon atoms, a phenyl group, a benzyl group, a vinylphenyl group, a haloalkyl group having 1 to 20 carbon atoms, a halophenyl group, an aminoalkyl group having 1 to 20 carbon atoms, a mercaptoalkyl group having 1 to 20 carbon atoms, a ureidoalkyl group having 2 to 20 carbon atoms, an isocyanatealkyl group having 2 to 8 carbon atoms, a group having 3 to 20 carbon atoms including an epoxy group, a group having 3 to 20 carbon atoms including an acrylamide group, a group having 4 to 20 carbon atoms including a methacrylamide group, an acetoxy group or -(CH2) n -OR 1 (R 1 represents a hydrogen atom, an alkali metal atom, an alkaline earth metal atom, an alkyl group having 1 to 20 carbon atoms, an alkenyl group having 2 to 20 carbon atoms, an acryloyl group, a methacryloyl group or a glycidyl group, and n represents an integer of 0 to 6. )

[0068]

[21] The dispersant according to

[20] , wherein the content of the structural unit represented by the formula (1) in the modified vinyl alcohol polymer is 0.01 mol% or more and less than 5 mol%;

[0069]

[22] The dispersant according to

[20] or

[21] , wherein the content of the structural unit represented by the above formula (1) in the above modified vinyl alcohol polymer is 90 mol% or more relative to the total structural units containing silicon atoms;

[0070]

[23] The dispersant according to

[20] ,

[21] or

[22] , wherein the modified vinyl alcohol polymer has a viscosity average degree of polymerization of 500 to 1500, and a saponification degree of 60 mol % to 90 mol %;

[0071]

[24] The dispersant according to any one of

[20] to

[23] , wherein the water-insoluble content of the modified vinyl alcohol polymer is 1000 ppm or less;

[0072]

[25] The dispersant according to any one of

[20] to

[24] , which is used for suspension polymerization;

[0073]

[26] A method for producing a vinyl polymer, comprising: a step of subjecting a vinyl compound to suspension polymerization in the presence of the dispersant according to any one of

[20] to

[25] ;

[0074]

[27] A mixture comprising a vinyl compound and the dispersant according to any one of

[20] to

[25] .

[0075] Effects of the Invention

[0076] According to the present application, a modified vinyl alcohol polymer having a polymer structure into which a silane coupling agent is introduced and which has excellent handleability and is useful in various applications; a method for producing the modified vinyl alcohol polymer, particles of the modified vinyl alcohol polymer, and an aqueous solution of the modified vinyl alcohol polymer can be provided.

[0077] In addition, according to the present application, a coating liquid capable of forming a coating layer having excellent silicone curability and adhesion to a substrate; a coated article, a molded body, and a release paper obtained by applying the coating liquid to a substrate can be provided.

[0078] Furthermore, according to the present application, a dispersant which can reduce the average particle size of the obtained vinyl polymer, reduce the amount of coarse particles, and reduce fish eyes by using it in the production process of the vinyl polymer; a method for producing the vinyl polymer and a mixture can be provided. DETAILED DESCRIPTION

[0079] <Modified vinyl alcohol polymer (modified PVA)>

[0080] The modified PVA of the present application has a structural unit represented by the following formula (1), and the water-insoluble component is 1000 ppm or less.

[0081] [Chemistry 7]

[0082]

[0083] In formula (1), X, Y and Z are each independently an alkyl group having 1 to 20 carbon atoms, an alkenyl group having 2 to 20 carbon atoms, a phenyl group, a benzyl group, a vinylphenyl group, a haloalkyl group having 1 to 20 carbon atoms, a halophenyl group, an aminoalkyl group having 1 to 20 carbon atoms, a mercaptoalkyl group having 1 to 20 carbon atoms, a ureidoalkyl group having 2 to 20 carbon atoms, an isocyanatealkyl group having 2 to 8 carbon atoms, a group having 3 to 20 carbon atoms including an epoxy group, a group having 3 to 20 carbon atoms including an acrylamide group, a group having 4 to 20 carbon atoms including a methacrylamide group, an acetoxy group or -(CH2) n -OR 1 (R 1 represents a hydrogen atom, an alkali metal atom, an alkaline earth metal atom, an alkyl group having 1 to 20 carbon atoms, an alkenyl group having 2 to 20 carbon atoms, an acryloyl group, a methacryloyl group or a glycidyl group, and n represents an integer of 0 to 6. )

[0084] The modified PVA of the present application has a polymer structure with a silane coupling agent introduced, and has few water-insoluble components and excellent water solubility. Therefore, it has excellent handling properties and is useful in various applications. That is, the modified PVA of the present application is easily dissolved when used in the form of an aqueous solution such as a coating liquid or a dispersant for suspension polymerization. In addition, there is little dissolved residue, so it is easy to handle. The modified PVA of the present application has excellent water solubility, and is therefore particularly useful in various applications in which it is dissolved in water for use in coating liquids, dispersants for suspension polymerization, and the like. In addition, as described above, the modified PVA with excellent water solubility can be stored and transported in a granular (powder) state, and can be dissolved in water and easily used, so it has excellent handling properties.

[0085] As X, Y, Z, or R 1 Examples of the alkyl group having 1 to 20 carbon atoms include methyl, ethyl, propyl, butyl, isobutyl, hexyl, and lauryl. The number of carbon atoms in these alkyl groups is preferably 1 to 6, and more preferably 1 to 3.

[0086] As X, Y, Z, or R 1 Examples of the alkenyl group having 2 to 20 carbon atoms include vinyl, allyl, hexenyl, and oleyl. The number of carbon atoms in these alkenyl groups is preferably 2 to 6, and more preferably 2 to 3. The alkenyl group is particularly preferably vinyl.

[0087] The vinylphenyl group represented by X, Y or Z means a group represented by CH2=CH-C6H4-.

[0088] Examples of the halogen contained in the halogenated alkyl group having 1 to 20 carbon atoms and the halogenated phenyl group represented by X, Y or Z include chlorine, bromine and fluorine. The halogenated alkyl group preferably has 1 to 6 carbon atoms, more preferably 1 to 3 carbon atoms.

[0089] The aminoalkyl group having 1 to 20 carbon atoms represented by X, Y or Z is usually NR2-C na H 2na -(R is independently a hydrogen atom or a hydrocarbon group having 1 to 6 carbon atoms. na is an integer of 1 to 20). The aminoalkyl group preferably has 1 to 10 carbon atoms, and more preferably 1 to 6 carbon atoms.

[0090] The mercaptoalkyl group having 1 to 20 carbon atoms represented by X, Y or Z is usually HS-C nb H 2nb - (nb is an integer of 1 to 20). The number of carbon atoms in the mercaptoalkyl group is preferably 1 to 6. The mercaptoalkyl group is particularly preferably a mercaptopropyl group.

[0091] The ureidoalkyl group having 2 to 20 carbon atoms represented by X, Y or Z is usually NH2CONH-C nc H2nc -(nc is an integer of 1 to 19). The ureidoalkyl group preferably has 2 to 6 carbon atoms.

[0092] The isocyanate alkyl group having 2 to 8 carbon atoms represented by X, Y or Z is usually OCN-C nd H 2nd - (nd is an integer of 1 to 7). The isocyanate alkyl group preferably has 2 to 6 carbon atoms.

[0093] The group having 3 to 20 carbon atoms and containing an epoxy group represented by X, Y or Z refers to a group having a cyclic ether structure containing a three-membered ring and having 3 to 20 carbon atoms. Examples of such a group include an epoxy group, a glycidyl group, a glycidyl group, a glycidyloxymethyl group, a 3-glycidyloxypropyl group, and a 2-(3,4-epoxycyclohexyl)ethyl group. The number of carbon atoms of the group containing an epoxy group is preferably 3 to 12.

[0094] Examples of the group having 3 to 20 carbon atoms and containing an acrylamide group represented by X, Y or Z include an acrylamide group, an acrylamidemethyl group, a 3-acrylamidepropyl group, a N-(2-acrylamideethyl)-aminopropyl group, and a (3-acrylamidepropyl)oxypropyl group. The group having 3 to 12 carbon atoms and containing an acrylamide group is preferably selected from the group having 3 to 12 carbon atoms.

[0095] Examples of the group having 4 to 20 carbon atoms and containing a methacrylamide group represented by X, Y or Z include a methacrylamide group, a methacrylamidemethyl group, a 3-methacrylamidepropyl group, an N-(2-methacrylamideethyl)-aminopropyl group, and a (3-methacrylamidepropyl)-oxypropyl group. The group having 4 to 12 carbon atoms and containing a methacrylamide group is preferably selected from the group having 4 to 12 carbon atoms.

[0096] As -(CH2) n -OR 1 The group shown is preferably a (meth)acryloyloxyalkyl group, and preferably a methacryloyloxypropyl group.

[0097] As R 1 The alkali metal atom shown is preferably a lithium atom, a sodium atom, a potassium atom, a rubidium atom, a cesium atom or a francium atom.

[0098] As R 1 The alkaline earth metal shown is preferably a magnesium atom, a calcium atom, a strontium atom or a barium atom.

[0099] At least one of X, Y and Z is preferably an alkenyl group having 2 to 20 carbon atoms, a mercaptoalkyl group having 1 to 20 carbon atoms or -(CH2) n -OR 1 The groups shown.

[0100] X, Y and Z are preferably an alkyl group having 1 to 20 carbon atoms, an alkenyl group having 2 to 20 carbon atoms, a phenyl group, a benzyl group, a vinylphenyl group, a haloalkyl group having 1 to 20 carbon atoms, a halophenyl group, an aminoalkyl group having 1 to 20 carbon atoms, a mercaptoalkyl group having 1 to 20 carbon atoms, a ureidoalkyl group having 2 to 20 carbon atoms, an isocyanatealkyl group having 2 to 8 carbon atoms, a group having 3 to 20 carbon atoms including an acrylamide group, a group having 4 to 20 carbon atoms including a methacrylamide group, an acetoxy group or -(CH2) n -OR 1 The group represented by is sometimes more preferably an alkyl group having 1 to 20 carbon atoms, an alkenyl group having 2 to 20 carbon atoms, a phenyl group, a benzyl group or -(CH2) n -OR 1 The group shown in the formula (a) is preferably an alkenyl group having 2 to 20 carbon atoms or -(CH2) n -OR 1 n is preferably an integer of 0 to 4 in some cases, and an integer of 0 to 2 in some cases.

[0101] The water-insoluble component of the modified PVA in the present application is less than 1000ppm. The upper limit of the water-insoluble component is preferably 500ppm, more preferably 200ppm, and further preferably 100ppm, 70ppm, 50ppm or 10ppm. As such, the modified PVA has less water-insoluble components, so it is excellent in handling and can exert excellent effects when used in coating liquids, dispersants, etc. The lower limit of the water-insoluble component can be 0ppm or 1ppm. The water-insoluble component in the present application refers to: the modified PVA is put into water in a concentration of 5% by mass, and the mass ratio of the dissolved residual component after stirring at 90°C for 60 minutes is specifically measured by the following method.

[0102] That is, a 500mL flask equipped with a stirrer and a reflux condenser is prepared in a water bath set to 20°C, 285g of distilled water is added to the flask, and stirring is started at 300rpm. 15g of modified PVA is weighed and slowly added to the flask. After the total amount of modified PVA (15g) is added, it takes 30 minutes to raise the temperature of the water bath to 90°C, thereby dissolving the modified PVA to obtain a modified PVA solution. After the temperature of the water bath reaches 90°C, the solution is further dissolved while stirring at 300rpm for 60 minutes. Thereafter, the modified PVA solution is used to filter the undissolved and residual solids of the modified PVA (hereinafter sometimes referred to as "insoluble solids" or "insoluble particles") using a metal filter with a mesh of 63μm. Next, the filter was washed with warm water at 90°C to remove the modified PVA solution attached to the filter, leaving only the insoluble solids on the filter, and then the filter was dried in a heating dryer at 120°C for 1 hour. The mass of the dried filter was compared with the mass of the filter before filtration to calculate the mass of the insoluble solids. The ratio of the mass of the insoluble solids to the mass (15 g) of the modified PVA initially added to the water was defined as the water-insoluble component.

[0103] The modified PVA of the present application is a polymer having a vinyl alcohol unit as a main structural unit. The lower limit of the ratio of the vinyl alcohol unit in the modified PVA relative to all structural units is, for example, sometimes preferably 30 mol%, more preferably 50 mol%, further preferably 65 mol%, further preferably 70 mol%, 80 mol%, 85 mol%, 90 mol% or 95 mol%. On the other hand, the upper limit of the ratio of the vinyl alcohol unit is, for example, sometimes preferably 99.9 mol%, more preferably 99 mol%, further preferably 98 mol%, 95 mol%, 90 mol%, 85 mol% or 80 mol%.

[0104] The modified PVA of the present application is obtained by, for example, reacting a silane coupling agent represented by formula (2) described later with PVA in the presence of an acid catalyst (post-modification) to react the -OR group of the silane coupling agent with the -OH group of PVA.

[0105] The lower limit of the amount of modification of the functional group derived from the silane coupling agent of the modified PVA is preferably 0.01 mol%, more preferably 0.1 mol%, and further preferably 0.2 mol%. By making the amount of modification of the functional group derived from the silane coupling agent above the above lower limit, it is easier to show the effect of the functional group derived from the silane coupling agent in the modified PVA. On the other hand, the upper limit of the amount of modification of the functional group derived from the silane coupling agent is preferably 5 mol%, more preferably 3 mol%, and further preferably 1 mol%. By making the amount of modification of the functional group derived from the silane coupling agent below the above upper limit, there is a tendency that the water solubility of the modified PVA is more excellent.

[0106] It should be noted that the modification amount in the present application refers to: in the modified PVA, the ratio of the total number of moles of functional groups derived from the silane coupling agent introduced by post-modification to the number of moles of all structural units possessed by the modified PVA, which is sometimes referred to as the "modification amount of functional groups derived from the silane coupling agent" or simply referred to as the "modification amount". It should be noted that in the present specification, the structure shown by -CR'2-CR'2- is set as 1 structural unit. The above R' is independently a hydrogen atom or an arbitrary substituent, and the two R' respectively contained in the same or different structural units are optionally bonded. For example, the structural unit shown by the above formula (1) is set to contain 1 structural unit. On the other hand, the vinyl alcohol unit, the residual vinyl ester unit, the structural unit derived from other monomers, etc. are each set to contain 1 structural unit. In other words, the structure corresponding to the monomer with a carbon-carbon double bond used in the polymerization is a structural unit.

[0107] The modification amount of the functional groups derived from the silane coupling agent can be determined by modifying the PVA 1 For example, in the case of modified PVA obtained by using a saponified product of polyvinyl acetate, that is, PVA and trimethoxyvinylsilane, the modified PVA is dissolved in DMSO-d6 and measured using a 400 MHz NMR. 1 H-NMR was used for measurement. The peak of hydrogen atoms contained in the hydroxyl group of the vinyl alcohol unit and the peak of hydrogen atoms bonded to the carbon atom bonded to the acetoxy group of the vinyl acetate unit are attributed to 4.2 to 5.2 ppm (integral value α). The peak of three hydrogen atoms contained in the vinyl group of trimethoxyvinylsilane is attributed to around 5.8 to 6.2 ppm (integral value β). Based on these integral values, the modification amount of the functional group derived from the silane coupling agent is calculated using the following formula.

[0108] Modification amount of functional groups derived from silane coupling agent (mol %) = {β / (3α+β)}×100

[0109] When other silane coupling agents are used, the modification amount can be similarly determined from the peak derived from the unreactive group in the silane coupling agent.

[0110] The lower limit of the content of the structural unit represented by the above formula (1) in the modified PVA of the present application is preferably 0.01 mol%, more preferably 0.1 mol%, and further preferably 0.2 mol%. By making the content of the structural unit represented by the above formula (1) above the above lower limit, it is easier to show the effect obtained by introducing a silane coupling agent into the modified PVA. On the other hand, the content of the structural unit represented by the above formula (1) is preferably less than 5 mol%. The upper limit of the content of the structural unit represented by the above formula (1) is more preferably 3 mol%, further preferably 2 mol%, and further preferably 1 mol%. By making the content of the structural unit represented by the above formula (1) less than the above upper limit or below the above upper limit, there is a tendency that the water solubility and handling properties of the modified PVA are better, and the performance is better when used in coating liquids and dispersants for suspension polymerization. The content of the structural unit represented by the above formula (1) can be adjusted by the modified PVA in the same way as the above modification amount. 1 For example, it is estimated that in the modified PVA obtained in each of the examples described below, the modification amount is substantially equal to the content of the structural unit represented by the formula (1).

[0111] In the modified PVA of the present application, the lower limit of the content of the structural unit shown in the above formula (1) relative to all structural units containing silicon atoms is preferably 90 mol%, more preferably 99 mol%, and the above content can be 100 mol%. For example, when a silane coupling agent with an epoxy group is reacted with PVA in a solution under a specified catalyst, the epoxy group reacts with the hydroxyl group of PVA. In this case, a structural unit containing silicon atoms different from the structural unit shown in the above formula (1) is sometimes formed, and the desired effect cannot be fully exerted. In contrast, by setting the content of the structural unit shown in the above formula (1) relative to all structural units containing silicon atoms to above the above lower limit, it has excellent water solubility, and coating liquids, dispersants, etc. are more suitable.

[0112] In the modified PVA, the lower limit of the block characteristic of the residual vinyl ester unit is preferably 0.30, and more preferably 0.40. On the other hand, the upper limit of the block characteristic is preferably 1, and more preferably 0.8. By making the block characteristic within the above range, it is easy to manufacture the modified PVA.

[0113] It should be noted that the above-mentioned block characteristics refer to the numerical values ​​representing the distribution of residual ester groups and hydroxyl groups generated by saponification of ester groups, and take values ​​between 0 and 2. 0 means that the residual ester groups or hydroxyl groups are completely distributed in blocks, and as the value increases, the alternation gradually increases. 1 means that the residual ester groups and hydroxyl groups exist completely randomly, and 2 means that the residual ester groups and hydroxyl groups exist completely alternately. The above-mentioned residual ester groups refer to: the ester groups (-OC(=O)-Q (Q represents the hydrocarbon groups contained in the vinyl ester monomers except the CH2=CH-OC(=O) part.)) contained in the vinyl ester monomer units in the modified PVA obtained after saponification. When the modified PVA contains structural units other than vinyl ester monomer units and / or vinyl alcohol units, the block characteristics are calculated based on all the continuous sites of the vinyl ester monomer units and / or vinyl alcohol units in the modified PVA.

[0114] The lower limit of the saponification degree of modified PVA is sometimes preferably 30 mol%, more preferably 65 mol%, further preferably 70 mol%, 80 mol% or 90 mol%. On the other hand, the upper limit of the saponification degree of the modified PVA is sometimes preferably 99.9 mol%, more preferably 99 mol%, further preferably 98 mol%, 93 mol%, 90 mol% or 85 mol%. By setting the saponification degree of modified PVA to the above range, a modified PVA with better water solubility can be obtained. The saponification degree of modified PVA and the raw material PVA described later are measured by the method described in JIS-K6726-1994.

[0115] The lower limit of the viscosity average degree of polymerization (hereinafter also referred to as "degree of polymerization") of the modified PVA is preferably 100, more preferably 300, further preferably 500, 600, 650, 700 or 1000. On the other hand, the upper limit is preferably 5000, more preferably 4000, further preferably 3000, 2000, 1500, 1000 or 800. The viscosity average degree of polymerization is measured by the method described in JIS-K6726-1994.

[0116] The modified PVA of the present application can be used for various applications. Examples thereof are listed below, but the applications of the modified PVA of the present application are not limited thereto.

[0117] (1) Use of vinyl chloride dispersant: Dispersion stabilizer and dispersing aid for suspension polymerization of vinyl chloride and vinylidene chloride

[0118] (2) Covering agent uses: sizing agent, fiber processing agent, leather finishing agent, coating, anti-fogging agent, anti-metal corrosion agent, galvanizing gloss agent, antistatic agent

[0119] (3) Adhesives and binders: Adhesives, adhesives, rewetting adhesives, various binders, additives for cement or mortar

[0120] (4) Applications of dispersion stabilizers: dispersion stabilizers for organic / inorganic pigments in coatings, adhesives, etc., dispersion stabilizers for emulsion polymerization of various vinyl compounds, post-emulsifiers for asphalt, etc.

[0121] (5) Paper processing applications: paper strength enhancers, oil / solvent resistance agents, smoothness enhancers, surface gloss improvers, fillers, barrier agents, light resistance enhancers, water resistance agents, dye / developer dispersants, adhesion improvers, adhesives

[0122] (6) Agricultural use: pesticide binders, pesticide spreaders, agricultural covering agents, soil conditioners, anti-ablation agents, pesticide dispersants

[0123] (7) Medical / cosmetic applications: granulation binders, coating agents, emulsifiers, patches, adhesives, film preparation base materials, film forming agents

[0124] (8) Viscosity modifier uses: thickener, rheology modifier

[0125] (9) Uses of agglomerators: agglomerators of suspended and dissolved matter in water, metal agglomerators

[0126] (10) Film applications: water-soluble film, polarizing film, barrier film, fiber product packaging film, seed health sheet, vegetation sheet, seed tape, hygroscopic film

[0127] (11) Uses of molded products: fibers, pipes, tubes, leak-proof films, water-soluble fibers for lace, sponges

[0128] (12) Application of resin raw materials: Raw materials for polyvinyl butyral, raw materials for photosensitive resins, raw materials for graft polymers, and raw materials for various gels

[0129] (13) Post-reaction uses: post-reaction uses with low molecular weight organic compounds, high molecular weight organic compounds and inorganic compounds.

[0130] Among them, as described later, the modified PVA of the present application is preferably used as a coating liquid for dispersants and paper processing applications, etc. In addition, the modified PVA is preferably used as a film, and more preferably as a film for unit packaging.

[0131] <Particles>

[0132] One embodiment of the modified PVA of the present application is particles (modified PVA particles). The particles of the present application are particles containing modified PVA. The particles have excellent water solubility and handleability and are useful in various applications. For example, the particles can be used to effectively obtain a coating liquid. In addition, the particles can also be effectively used as a dispersant. The particles can be particles that are essentially composed only of modified PVA. The content of the modified PVA in the particles is, for example, 90% by mass or more, 99% by mass or more, or 100% by mass.

[0133] The average particle size (dp50) of the particles of the present application is, for example, preferably 100 μm or more and 5 mm or less, more preferably 200 μm or more and 3 mm or less, and further preferably 300 μm or more and 1 mm or less. When the average particle size is within the above range, there is a tendency for higher handling properties. The average particle size (dp50) is calculated as follows: using a JIS standard sieve, the particle size distribution is measured by the dry sieving method described in JIS-Z8815-1994, and the result is plotted in the Rosin-Rammler distribution for calculation.

[0134] The dispersion degree A of silicon atoms in the particles is preferably 0.2 or more and less than 1. The dispersion degree A of silicon atoms in the particles is the ratio of the silicon atom content in the center of the particle in the modified PVA in a particle state to the silicon atom content on the surface of the particle, and serves as an index of the dispersion degree of the functional groups derived from the silane coupling agent in the polymer of the modified PVA. Specifically, the dispersion degree A is measured by the following method.

[0135] First, 10 particles with a particle size of 100 μm or more and approximately spherical are selected. These particles are divided into two equal parts in such a way that the cross-sectional area is the largest. The center of the inscribed circle of the cross section is taken as the center of the particle, and the point of intersection between the inscribed circle and the particle surface is taken as the particle surface. The silicon atom content is measured using an energy dispersive X-ray analyzer (EDS). For each particle, the dispersion A of each particle is calculated according to the following formula, and the average value of the 10 particles is used.

[0136] Dispersion A = Silicon atom content in the center of the particle (mol %) / Silicon atom content on the surface of the particle (mol %)

[0137] The lower limit of the dispersion degree A is preferably 0.2, more preferably 0.5, further preferably 0.7, further preferably 0.8, and further preferably 0.9. In addition, the dispersion degree A may be less than 1, and the upper limit value may be 0.99. By making the dispersion degree A within the above range, the dispersion degree of the functional groups derived from the silane coupling agent in the polymer or particles of the modified PVA becomes better, and the water solubility and handling property of the modified PVA can be made more excellent. In addition, the dispersion degree A is within the above range and the result of high water solubility can be suitably used in coating liquids, dispersants, etc., as a coating liquid, a dispersant, etc. Performance improvement.

[0138] <Aqueous solution>

[0139] The aqueous solution of the present application contains the modified PVA of the present application. The insoluble components of the modified PVA in the aqueous solution of the present application are small, and it can be suitably used as a coating liquid, etc. That is, the coating liquid, etc. described later are one form of the aqueous solution. The aqueous solution can be obtained by dissolving the modified PVA in water using a conventionally known method.

[0140] The aqueous solution of the present application does not contain a silane coupling agent or further contains a silane coupling agent, and the content of silicon atoms contained in the modified PVA relative to the total content of silicon atoms contained in the modified PVA and the silane coupling agent is sometimes preferably 50 mol% or more. The lower limit of the content ratio of the above silicon atoms is more preferably 70 mol%, 90 mol% or 95 mol%. In the aqueous solution, when the content of the silane coupling agent is so small, there is a tendency to improve the storage stability of the aqueous solution, the reaction uniformity, etc.

[0141] The aqueous solution may contain only modified PVA as a solute. The modified PVA in the aqueous solution preferably contains 50% by mass or more, more preferably 70% by mass or more, more preferably 90% by mass or more, and more preferably 95% by mass or more relative to the total solute. The concentration of the modified PVA in the aqueous solution is appropriately set according to the purpose, for example, it may be 0.1% by mass or more and 30% by mass or less, or it may be 1% by mass or more and 25% by mass or less. The aqueous solution may further contain a solvent other than water.

[0142] <Method for producing modified PVA>

[0143] The modified PVA can be produced, for example, by saponifying a vinyl ester polymer obtained by polymerizing a vinyl ester monomer to obtain PVA, and then reacting the PVA with a silane coupling agent.

[0144] Examples of the vinyl ester monomers include vinyl formate, vinyl acetate, vinyl propionate, vinyl valerate, vinyl caprate, vinyl laurate, vinyl stearate, vinyl benzoate, vinyl pivalate, vinyl versatate, etc. Among them, vinyl acetate is preferred.

[0145] As a method for polymerizing vinyl ester monomers, known methods such as bulk polymerization, solution polymerization, suspension polymerization, and emulsion polymerization can be cited. Among these methods, bulk polymerization under solvent-free conditions and solution polymerization using alcohol and other solvents are preferred. From the viewpoint of improving the effect of the present application, solution polymerization in the presence of lower alcohols is more preferred. As the above-mentioned lower alcohol, alcohols with a carbon number of 3 or less are preferred, and methanol, ethanol, n-propanol and isopropanol are more preferred, and methanol is further preferred. When the polymerization reaction is carried out by bulk polymerization or solution polymerization, the reaction method can also be any method in intermittent and continuous.

[0146] As the initiator used in the polymerization reaction, for example, azo initiators such as 2,2'-azobisisobutyronitrile, 2,2'-azobis(2,4-dimethylvaleronitrile), 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile); organic peroxide initiators such as benzoyl peroxide and n-propyl peroxycarbonate, and other well-known initiators can be listed. The polymerization temperature during the polymerization reaction is not particularly limited, but is preferably in the range of 5°C or more and 200°C or less.

[0147] When the vinyl ester monomer is polymerized, a copolymerizable monomer may be further copolymerized within the scope that does not impair the main purpose of the present application. In addition, the copolymerizable monomer may be a silane coupling agent. Examples of such monomers include α-olefins such as ethylene, propylene, 1-butene, isobutylene, and 1-hexene; acrylamide derivatives such as N-methylacrylamide and N-ethylacrylamide; methacrylamide derivatives such as N-methylmethacrylamide and N-ethylmethacrylamide; vinyl ethers such as methyl vinyl ether, ethyl vinyl ether, n-propyl vinyl ether, isopropyl vinyl ether, and n-butyl vinyl ether; vinyl ethers containing hydroxyl groups such as ethylene glycol vinyl ether, 1,3-propylene glycol vinyl ether, and 1,4-butanediol vinyl ether; allyl acetate; propylene allyl ether, butyl allyl ether, hexyl allyl ether, and the like; Propyl ether; monomers having an oxyalkylene group; isopropenyl acetate; α-olefins containing a hydroxyl group such as 3-butene-1-ol, 4-pentene-1-ol, 5-hexene-1-ol, 7-octen-1-ol, 9-decen-1-ol, 3-methyl-3-butene-1-ol; monomers having a silyl group such as vinyltrimethoxysilane, vinylmethyldimethoxysilane, vinyldimethylmethoxysilane, vinyltriethoxysilane, vinylmethyldiethoxysilane, vinyldimethylethoxysilane, 3-(meth)acrylamidepropyltrimethoxysilane, 3-(meth)acrylamidepropyltriethoxysilane, etc. The upper limit of the amount of these monomers used varies depending on the purpose and application of the monomers, but is preferably 20 mol% relative to the total monomers, and more preferably 10 mol%.

[0148] In the saponification reaction of the vinyl ester polymer obtained by the above-mentioned polymerization process, an alkali catalyst or an acid catalyst can be used. For example, the alcoholysis-hydrolysis reaction using an alkaline catalyst such as sodium hydroxide, potassium hydroxide, sodium methoxide, etc., which is known in the art, can be applied. As the solvent used in the saponification reaction, there can be listed alcohols such as methanol and ethanol; esters such as methyl acetate and ethyl acetate; ketones such as acetone and methyl ethyl ketone; aromatic hydrocarbons such as benzene and toluene, etc., which can be used alone or in combination of two or more. Among them, it is convenient to use methanol or a mixed solution of methanol and methyl acetate as a solvent and to carry out the saponification reaction in the presence of sodium hydroxide as an alkaline catalyst, so it is preferred. PVA can be obtained by this method.

[0149] From the viewpoint of being able to further suppress excessive cross-linking of the obtained modified PVA, the viscosity of a 4 mass% aqueous solution of PVA before reacting with a silane coupling agent (hereinafter sometimes referred to as "raw PVA") is preferably from 1 mPa·s to 200 mPa·s, more preferably from 2 mPa·s to 100 mPa·s, and even more preferably from 3 mPa·s to 50 mPa·s.

[0150] The lower limit of the saponification degree of the raw material PVA is sometimes preferably 30 mol%, more preferably 60 mol%, further preferably 65 mol%, further preferably 70 mol%, 80 mol% or 90 mol%. On the other hand, the upper limit of the saponification degree of the raw material PVA is sometimes preferably 99.9 mol%, more preferably 99 mol%, further preferably 98 mol%, 93 mol%, 90 mol% or 85 mol%. By setting the saponification degree of the raw material PVA to the above range, it is expected that the reaction with the silane coupling agent can be carried out more efficiently.

[0151] The lower limit of the polymerization degree of the raw material PVA is preferably 100, more preferably 300, further preferably 500, 600, 650, 700 or 1000. On the other hand, the upper limit is preferably 5000, more preferably 4000, further preferably 3000, 2000, 1500, 1000 or 800.

[0152] For example, the modified PVA can be obtained by reacting the above-mentioned raw material PVA with a silane coupling agent (post-modification).

[0153] As the silane coupling agent, it is preferable to use a compound represented by the following formula (2).

[0154] [Chemistry 8]

[0155]

[0156] In formula (2), R is an alkyl group having 1 to 8 carbon atoms, an acetyl group or -(CH2) m -OR 2 (R 2 represents an alkyl group having 1 to 20 carbon atoms, and m represents an integer of 1 to 6. ). X, Y and Z are each independently an alkyl group having 1 to 20 carbon atoms, an alkenyl group having 2 to 20 carbon atoms, a phenyl group, a benzyl group, a vinylphenyl group, a haloalkyl group having 1 to 20 carbon atoms, a halophenyl group, an aminoalkyl group having 1 to 20 carbon atoms, a mercaptoalkyl group having 1 to 20 carbon atoms, a ureidoalkyl group having 2 to 20 carbon atoms, an isocyanatealkyl group having 2 to 8 carbon atoms, a group having 3 to 20 carbon atoms including an epoxy group, a group having 3 to 20 carbon atoms including an acrylamide group, a group having 4 to 20 carbon atoms including a methacrylamide group, an acetoxy group or -(CH2) n- OR 1 (R 1 represents an alkyl group having 1 to 20 carbon atoms, an alkenyl group having 2 to 20 carbon atoms, an acryloyl group, a methacryloyl group or a glycidyl group, and n represents an integer of 0 to 6. )

[0157] R in formula (2) is preferably an alkyl group having 1 to 8 carbon atoms, and more preferably an alkyl group having 1 to 3 carbon atoms. Specific aspects and suitable aspects of X, Y and Z in formula (2) include the specific aspects and suitable aspects of X, Y and Z in formula (1).

[0158] Examples of the compound represented by formula (2) include vinyltrimethoxysilane, vinylmethyldimethoxysilane, vinyldimethylmethoxysilane, vinyltriethoxysilane, vinylmethyldiethoxysilane, vinyldimethylethoxysilane, allyltrimethoxysilane, allylmethyldimethoxysilane, allyltriethoxysilane, allylmethyldiethoxysilane, allyldimethylethoxysilane, vinyltri(β-methoxyethoxy)silane, vinylisobutyldimethoxysilane, vinylethyldimethoxysilane, vinylmethoxybisbutyloxysilane, and vinyldimethoxybutoxysilane. 、vinyltributoxysilane, vinylmethoxydihexyloxysilane, vinyldimethoxyhexyloxysilane, vinyltrihexyloxysilane, vinylmethoxydioctyloxysilane, vinyldimethoxyoctyloxysilane, vinyltrioctyloxysilane, vinylmethoxydilauryloxysilane, vinyldimethoxylauryloxysilane, vinylmethoxydioleyloxysilane, vinyldimethoxyoleyloxysilane, 3-(meth)acrylamide-propyltrimethoxysilane, 3-(meth)acrylamide-propyltriethoxysilane, 3-(meth)acrylamide-propyltri(β-methoxyethoxy)silane, 2-(meth)acrylamide-ethyltrimethoxy trimethoxysilane, 1-(meth)acrylamide-methyltrimethoxysilane, 2-(meth)acrylamide-2-methylpropyltrimethoxysilane, 2-(meth)acrylamide-isopropyltrimethoxysilane, N-(2-(meth)acrylamide-ethyl)-aminopropyltrimethoxysilane, (3-(meth)acrylamide-propyl)-oxypropyltrimethoxysilane, 3-(meth)acrylamide-propyltriacetoxysilane, 2-(meth)acrylamide-ethyltriacetoxysilane, 4-(meth)acrylamide-butyltriacetoxysilane, 3-(meth)acrylamide-propyltripropionyloxysilane, 2-(meth)acrylamide-2- Methylpropyl triacetoxysilane, N-(2-(meth)acrylamide-ethyl)-aminopropyl triacetoxysilane, 3-(meth)acrylamide-propyl isobutyl dimethoxysilane, 2-(meth)acrylamide-ethyl dimethyl methoxysilane, 3-(meth)acrylamide-propyl methyl diacetoxysilane, 2-(meth)acrylamide-2-methylpropyl hydrogen dimethoxysilane, 3-(N-methyl-(meth)acrylamide)-propyl trimethoxysilane, 2-(N-ethyl-(meth)acrylamide)-ethyl triacetoxysilane, p-phenylenediyl trimethoxysilane (silane coupling agent having vinylphenyl group), 2-(3,3-(4-epoxycyclohexyl)ethyl trimethoxysilane, 3-glycidoxypropyl methyl dimethoxysilane, 3-glycidoxypropyl trimethoxysilane, 3-glycidoxypropyl methyl diethoxysilane, 3-glycidoxypropyl triethoxysilane, 3-methacryloxypropyl methyl dimethoxysilane, 3-methacryloxypropyl trimethoxysilane, 3-methacryloxypropyl methyl diethoxysilane, 3-methacryloxypropyl triethoxysilane, 3-acryloxypropyl trimethoxysilane, 3-aminopropyl trimethoxysilane, 3-aminopropyl triethoxysilane, N-phenyl-3-aminopropyl trimethoxysilane, 3-ureidopropyl trimethoxysilane, 3-ureidopropyl triethoxysilane, 3-isocyanate propyl triethoxysilane, 3-mercaptopropyl methyl dimethoxysilane, 3-mercaptopropyl trimethoxysilane, and the like. Among them, vinyltrimethoxysilane is preferably used because it is easy to produce industrially and can be obtained at a low cost.

[0159] For example, the modified PVA can be obtained by causing a condensation reaction between the OR group of the silane coupling agent represented by the above formula (2) and the OH group of PVA to form a structural unit represented by the formula (1).

[0160] The lower limit of the amount of the silane coupling agent added is preferably 0.1 parts by mass, more preferably 0.5 parts by mass, and further preferably 1 part by mass relative to 100 parts by mass of PVA. On the other hand, the upper limit of the amount of the silane coupling agent added is preferably 20 parts by mass, more preferably 15 parts by mass, and further preferably 10 parts by mass relative to 100 parts by mass of PVA. By making the amount of the silane coupling agent added within the above range, the water solubility and handling property of the obtained modified PVA can be further improved.

[0161] The method for reacting PVA with the silane coupling agent is not particularly limited, and the target reaction can be carried out by mixing powdered or granular PVA with a solution containing a silane coupling agent using, for example, a ribbon blender, a Henschel mixer, a V-type blender, a rotary furnace, a planetary mixer, a high-speed stirrer, a Henschel mixer, a paddle mixer, a Lödiger agitator, or the like.

[0162] In addition, one embodiment of the present application is a method for producing a modified PVA, including a step of impregnating a solid PVA with a silane coupling agent.

[0163] Moreover, one embodiment of the present application is a production method in which, in the impregnation step, a solution containing a silane coupling agent is sprayed onto PVA to allow the PVA to be impregnated (permeated).

[0164] In the above-mentioned impregnation process, it is preferred to use a solvent so that the silane coupling agent is uniformly dispersed in the PVA. That is, it is preferably a method in which a solvent (solution) containing a silane coupling agent is added to the PVA particles to react a mixture containing PVA and the silane coupling agent. At this time, the amount of solvent added is not limited, and is preferably 10 to 50 parts by mass relative to 100 parts by mass of PVA. By making the amount of solvent added in the above-mentioned range, there is a tendency that the silane coupling agent is more uniformly impregnated into the PVA particles, and then, the reaction of the silane coupling agent and PVA is more uniformly carried out, and the water solubility and handleability of the resulting modified PVA are further improved.

[0165] The average particle size (dp50) of the PVA particles used in the impregnation step is preferably 100 μm or more and 5 mm or less, more preferably 200 μm or more and 3 mm or less, and even more preferably 300 μm or more and 1 mm or less. By using PVA particles of such a size, there is a tendency that the silane coupling agent is more uniformly impregnated into the PVA particles, and the water solubility and handling properties of the resulting modified PVA are further improved.

[0166] In addition, an acidic catalyst is preferably used in the above-mentioned impregnation step. As usable acidic catalysts, inorganic acids such as sulfuric acid, hydrochloric acid, and phosphoric acid; organic acids such as acetic acid and p-toluenesulfonic acid can be used. If a substance with high acidity is used, a saponification reaction of PVA may sometimes proceed. Therefore, it is preferred to use an acidic catalyst having an acid dissociation constant pKa of 4 to 6. Among them, acetic acid is preferably used.

[0167] As the solvent that can be used in the above-mentioned impregnation step, a polar solvent with high affinity for PVA is preferred. For example, various solvents such as alcohols such as methanol, ethanol, and isopropanol; ketones such as acetone, methyl ethyl ketone, and diethyl ketone; esters such as methyl acetate and ethyl acetate; dimethyl sulfoxide, N,N-dimethylformamide, etc. can be used. Among these, methanol and methyl acetate are preferred.

[0168] In addition, one embodiment of the manufacturing method of the modified PVA of the present application also has: a step of heat-treating the PVA impregnated with a silane coupling agent obtained in the impregnation step. The reaction between the silane coupling agent and the PVA fully occurs through the heat treatment. When the PVA impregnated with the silane coupling agent is heat-treated, the dehydration condensation reaction between the OR group of the silane coupling agent and the OH group of the PVA is promoted due to drying, and the formation of the structural unit shown in the above formula (1) fully occurs. It should be noted that it can be considered that when the solution containing the silane coupling agent and PVA is heat-treated, the dehydration condensation reaction will not be fully carried out, and the formation of the structural unit shown in the above formula (1) will hardly occur.

[0169] The means of the above-mentioned heat treatment is not particularly limited, for example, a drying machine can be used for heat treatment, preferably a hot air drying machine is used for heat treatment. In addition, the infiltration process and the heat treatment process can be carried out simultaneously, for example, a ribbon blender, a Henschel mixer, a V-blender, a rotary furnace, a planetary motion mixer, a high-speed stirrer, a Henschel mixer, a paddle mixer, a Lödiger agitator, etc. can be used to mix the powdered or granular PVA with a solution containing a silane coupling agent and heat-treat it.

[0170] In the step of heat-treating the PVA and the silane coupling agent, the lower limit of the heat treatment temperature (reaction temperature) is preferably 20° C., more preferably 40° C., further preferably 60° C., further preferably 75° C., and particularly preferably 80° C. On the other hand, the upper limit of the heat treatment temperature is preferably 120° C., more preferably 110° C., and further preferably 100° C. By setting the heat treatment temperature to the above range, the reaction proceeds more satisfactorily, and the water solubility and handling properties of the obtained modified PVA can be further improved.

[0171] In the above-mentioned heat treatment step, the heat treatment time can be appropriately set according to the heat treatment temperature, preferably more than 1 hour and less than 18 hours, more preferably more than 3 hours and less than 12 hours. In addition, it is preferred to react for more than 3 hours and less than 12 hours at a heat treatment temperature of more than 70°C and less than 90°C.

[0172] By the above-mentioned manufacturing method, the silane coupling agent is impregnated into the solid PVA to make the PVA swell, and the PVA and the silane coupling agent react in this state, thereby suppressing the unevenness of the functional groups derived from the silane coupling agent in the modified PVA, and as a result, it is possible to obtain modified PVA particles with a higher dispersion degree A. In addition, the water-insoluble components in this modified PVA are less, and the water solubility and handling properties are better, so it is easier to apply to various purposes. For example, when used in a coating liquid, a dispersant, etc., it can exert excellent performance as a coating liquid, a dispersant, etc.

[0173] <Coating liquid>

[0174] The coating liquid of the present application contains a modified PVA having a structural unit shown in the above formula (1). The coating liquid of the present application is preferably a coating liquid for a paper substrate or a film substrate, and can be a coating liquid used when manufacturing a release paper or a release film. The coating liquid can form a coating layer with excellent silicone curing properties and adhesion to the substrate. In addition, the coating layer formed by the coating liquid also has sufficient filling properties. The specific form and suitable form of the modified PVA used in the coating liquid are the same as the modified PVA of the present application above, except that the water-insoluble component does not need to be less than 1000ppm. Among them, the water-insoluble component of the modified PVA used in the coating liquid is preferably within the above-mentioned range.

[0175] The viscosity average polymerization degree of the modified PVA used in the coating liquid of the present application is not particularly limited, and its lower limit is sometimes preferably 500, more preferably 600, and further preferably 650. By setting the lower limit of the viscosity average polymerization degree of the modified PVA to the above range, there is a tendency that the air permeability resistance and the packing property of the coating layer formed by the coating liquid containing the modified PVA are improved. In addition, the upper limit of the viscosity average polymerization degree is sometimes preferably 5000, more preferably 4000, further preferably 3000, and further preferably 2000. By setting the upper limit of the viscosity average polymerization degree of the modified PVA to the above range, the productivity of the modified PVA can be further improved. In addition, the viscosity average polymerization degree of the modified PVA is preferably above 500 and below 5000.

[0176] The lower limit of the saponification degree of the modified PVA used in the coating liquid of the present application is sometimes preferably 70 mol%, more preferably 80 mol%, and further preferably 90 mol%. On the other hand, the upper limit of the saponification degree of the modified PVA is preferably 99.9 mol%. By setting the saponification degree of the modified PVA to the above range, a modified PVA with excellent water solubility and water resistance of the coating film after coating and drying can be obtained, and the performance as a coating liquid is more excellent.

[0177] The upper limit of the insoluble components of the modified PVA in the coating liquid is sometimes preferably 1000ppm, more preferably 500ppm, further preferably 200ppm, further preferably 100ppm, particularly preferably 70ppm, more particularly preferably 50ppm, and further particularly preferably 10ppm. In addition, the lower limit of the insoluble components of the modified PVA in the coating liquid is preferably 0ppm, and can be 1ppm. It should be noted that the insoluble components of the modified PVA in the coating liquid of the present application refer to the mass ratio of the components derived from the modified PVA dissolved and remaining in the coating liquid, and are specifically measured by the following method.

[0178] The coating liquid was passed through a metal filter with a mesh size of 63 μm, and the filter was further washed with warm water at 90° C. to obtain the solid of the modified PVA remaining in the coating liquid without being dissolved. The ratio of the mass of the solid of the insoluble modified PVA to the mass of the modified PVA contained in the coating liquid before filtration was calculated and taken as the insoluble component of the modified PVA in the coating liquid.

[0179] The lower limit of the concentration of the modified PVA in the coating liquid is sometimes preferably 2 mass %, more preferably 5 mass %. In addition, the upper limit of the concentration of the modified PVA in the coating liquid is sometimes preferably 30 mass %, more preferably 25 mass %. By making the concentration of the modified PVA in the coating liquid the above range, the coating efficiency is further improved, and the high-speed coating property is more excellent.

[0180] The coating liquid of the present application does not contain a silane coupling agent or further contains a silane coupling agent, and the content of silicon atoms contained in the modified PVA relative to the total content of silicon atoms contained in the modified PVA and the silane coupling agent is sometimes preferably 50 mol% or more. The lower limit of the content ratio of the above-mentioned silicon atoms is more preferably 70 mol%, 90 mol% or 95 mol%. In the coating liquid, when the content of the silane coupling agent is so small, there is a tendency to improve the storage stability and reaction uniformity of the coating liquid.

[0181] The coating solution of the present application is preferably an aqueous solution containing modified PVA. In this case, the aqueous solution may contain a small amount of organic solvent, and may also contain a small amount of water-insoluble organic particles and inorganic particles. The concentration of the modified PVA in the aqueous solution is preferably 1% by mass or more and 30% by mass or less.

[0182] The method for producing the coating liquid of the present application is not particularly limited. The coating liquid can be obtained, for example, by dissolving particles of modified PVA in water.

[0183] The coating liquid may contain other components in addition to the vinyl alcohol polymer of the present application within the range that does not impair the effect of the present application. Other components include aqueous dispersible resins such as SBR latex, NBR latex, vinyl acetate emulsion, ethylene / vinyl acetate copolymer emulsion, (meth)acrylate emulsion, vinyl chloride emulsion, etc.; raw starch obtained from wheat, corn, rice, potato, sweet potato, cassava, sago, etc.; raw starch decomposition products such as oxidized starch and dextrin; starch derivatives such as etherified starch, esterified starch, and cationic starch; cellulose derivatives such as methyl cellulose, hydroxyethyl cellulose, and carboxymethyl cellulose (CMC); monosaccharides such as glucose, fructose, isomerized sugar, and xylose; Disaccharides such as maltose, lactose, sucrose, trehalose, palatinose, reduced maltose, reduced palatinose, reduced lactose; oligosaccharides such as starch syrup, isomalto-oligosaccharide, fructooligosaccharide, lactose oligosaccharide, soybean oligosaccharide, xylooligosaccharide, coupling sugar, cyclodextrin compounds; polysaccharides such as Prussian polysaccharide, pectin, agar, glucomannan, polydextrose, xanthan gum; albumin, gelatin, casein, gum arabic, polyamide resin, melamine resin, poly(meth)acrylamide, polyvinyl pyrrolidone, sodium poly(meth)acrylate, anion-modified PVA, sodium alginate, water-soluble polyester, etc.

[0184] The content of these components in the coating liquid is usually 10% by mass or less.

[0185] The coating liquid may contain pigments within a range that does not impair the effects of the present application. Examples of pigments include inorganic pigments (clay, kaolin, aluminum hydroxide, calcium carbonate, talc, etc.) and organic pigments (plastic pigments, etc.) commonly used in the field of coated paper manufacturing. The content of these pigment components in the coating liquid is preferably 50% by mass or less.

[0186] <Coating>

[0187] A suitable embodiment of the present application is a coating obtained by applying the coating liquid to the surface of a substrate. As the substrate, a paper substrate or a film substrate is preferred. The method for manufacturing the coating is not particularly limited, and may be, for example, a method comprising the following steps: a step of applying the coating liquid to the substrate, and a step of drying the substrate after coating.

[0188] As the paper substrate, known paper or synthetic paper obtained by papermaking from chemical pulp such as hardwood kraft pulp and softwood kraft pulp, GP (grinded wood pulp), RGP (refined pulp), TMP (thermomechanical pulp) and other mechanical pulps can be used. In addition, as the paper substrate, high-quality paper, medium-quality paper, alkaline paper, glass paper, semi-glass paper, or paperboard, white paperboard used for corrugated cardboard, building materials, whiteboard, particleboard and the like can also be used. It should be noted that the paper substrate may contain organic pigments and inorganic pigments, as well as papermaking auxiliary chemicals such as paper strength enhancers, sizing agents, and yield improvers. In addition, the paper substrate may be subjected to various surface treatments.

[0189] The film substrate is preferably a film substrate composed of a thermoplastic resin. Examples of the thermoplastic resin include polyolefins, polyesters, and polyamides.

[0190] Examples of coating equipment include a 2-roll sizing machine, a gate roll sizing machine, a metering sizing machine, an air knife coater, a rod coater, a roller coater, a blade coater, and the like. The coating speed is preferably 100 to 2,000 m / min. In addition, the coating speed is sometimes more preferably 300 m / min or more, and more preferably 1,800 m / min or less. By setting the coating speed within this range, production efficiency can be further improved, and uniform coating is easier. The coating amount can be arbitrarily selected according to the properties of the paper, and is preferably 0.05 to 10 g / m2 relative to a single side of the paper. 2 about.

[0191] Drying after coating can be performed by, for example, hot air, infrared rays, heating cylinders, or a combination thereof. The dried coating can be further improved in barrier properties by humidity control and calendering. As humidity control conditions, it is desirable to use conditions such that the moisture content in the paper is 5 to 20% by mass. In addition, as calendering conditions, the roll temperature is preferably room temperature to 200°C, and the roll line pressure is preferably 20 to 350 kg / cm.

[0192] The lower limit of the air permeability resistance of the coating is preferably 400 seconds, more preferably 2,000 seconds, further preferably 5,000 seconds, further preferably 7,000 seconds, and particularly preferably 10,000 seconds. The upper limit of the air permeability resistance of the coating is not particularly limited, and may be 20,000 seconds.

[0193] As the coating, there can be listed release paper base paper, barrier paper, oil-resistant paper, wrapping paper, cardboard, polyethylene release film, polypropylene release film, polyester release film, etc. Among them, the release paper base paper formed by coating the coating liquid on the surface of the paper substrate is a suitable embodiment of the present application. A release layer (peeling layer) can be formed on the surface of the release paper base paper. When forming the release layer, it is suitable to use solvent-based silicone and non-solvent-based (emulsion-based, oligomer-based) silicone. Since the solvent-based silicone contains a solvent (toluene, etc.), the release paper base paper of the present application preferably has a barrier property for the solvent. In addition, when using non-solvent-based silicone, water resistance is sometimes required, so the release paper base paper of the present application preferably has water resistance. In the present application, a release paper having the release paper base paper and a release layer formed on the surface of the release paper base paper is also a suitable embodiment.

[0194] <molded body>

[0195] One embodiment of the present application is a formed article including a layer containing a modified PVA having a structural unit represented by the following formula (1′).

[0196] [Chemistry 9]

[0197]

[0198] In formula (1'), X, Y and Z are each independently an alkyl group having 1 to 20 carbon atoms, an alkenyl group having 2 to 20 carbon atoms, a phenyl group, a benzyl group, a vinylphenyl group, a haloalkyl group having 1 to 20 carbon atoms, a halophenyl group, an aminoalkyl group having 1 to 20 carbon atoms, a mercaptoalkyl group having 1 to 20 carbon atoms, a ureidoalkyl group having 2 to 20 carbon atoms, an isocyanatealkyl group having 2 to 8 carbon atoms, a group having 3 to 20 carbon atoms including an epoxy group, a group having 3 to 20 carbon atoms including an acrylamide group, a group having 4 to 20 carbon atoms including a methacrylamide group, an acetoxy group or -(CH2) n- OR 1 (R 1 represents a hydrogen atom, an alkali metal atom, an alkaline earth metal atom, an alkyl group having 1 to 20 carbon atoms, an alkenyl group having 2 to 20 carbon atoms, an acryloyl group, a methacryloyl group, a glycidyl group or a linking bond, and n represents an integer of 0 to 6. )

[0199] The specific form and suitable form of the structural unit represented by formula (1') include R 1The specific form and suitable form of the structural unit represented by the above formula (1) are the same except that the cross-linked structure is optionally formed in the case of a connecting bond. In addition, the specific form and suitable form of the modified PVA contained in the molded body are the same as the specific form and suitable form of the modified PVA used in the coating liquid of the present application, etc., except that the cross-linked structure is optionally formed.

[0200] The molded body is not particularly limited, and for example, it can be a three-dimensional object or a sheet. The material constituting the molded body is not particularly limited, and for example, metal, ceramic, glass, resin, concrete, etc. can be listed. The metal can be, for example, iron, steel, aluminum, stainless steel, gold, silver, copper, etc. In addition, the molded body can be the above-mentioned substrate, and as the substrate, it is preferably a paper substrate or a film substrate.

[0201] The layer containing modified PVA in the molded article may be a coating film formed by applying the above-mentioned coating liquid to the molded article to be formed.

[0202] The content of the modified PVA in the layer containing the modified PVA may be, for example, 50% by mass or more and 100% by mass or less, or 70% by mass or more and 99.9% by mass or less. The layer containing the modified PVA may further contain other components except the modified PVA. As other components, various components that may be contained in the above-mentioned coating solution may be listed.

[0203] <Release Paper>

[0204] One embodiment of the present application is a release paper. The release paper comprises a substrate, a silicone filling layer and a release layer, wherein the silicone filling layer comprises a modified PVA having a structural unit represented by the above formula (1'). The release paper is preferably laminated with a substrate, a silicone filling layer and a release layer in this order. The release paper of the present application is a form of the molded body of the present application. That is, the silicone filling layer of the release paper of the present application corresponds to the layer comprising the modified PVA in the above molded body.

[0205] The release layer preferably contains addition silicone and platinum, and the content of platinum is preferably 0.001 to 0.05 parts by mass relative to 100 parts by mass of the addition silicone. This can further improve the curability of the addition silicone in the release layer. In addition, the curing speed of the addition silicone can be accelerated, so the time required for the silicone curing process can be shortened or the amount of platinum can be reduced, and it can be expected to reduce the manufacturing cost.

[0206] As the base material in the release paper, for example, the above-mentioned base materials can be cited, and paper base materials and film base materials can be suitably used. It should be noted that in the present application, in the release paper having a base material, a silicone filling layer and a release layer, even in the case where the base material is composed of only a film base material, it is sometimes referred to as "release paper".

[0207] <Dispersant>

[0208] The dispersant of the present application comprises a modified PVA having a structural unit shown in the above formula (1). The vinyl polymer manufactured using the dispersant has a small average particle size, a small amount of coarse particles and few fish eyes. The specific form and suitable form of the modified PVA used in the dispersant are the same as those of the modified PVA of the present application above, except that the water-insoluble component does not need to be less than 1000ppm. Among them, the water-insoluble component of the modified PVA used in the dispersant is preferably within the above range.

[0209] The content of the modified PVA in the dispersant of the present application is sometimes preferably 50% by mass or more, more preferably 80% by mass or more, further preferably 90% by mass or more, and further preferably 95% by mass or more. In addition, the content of the modified PVA in the dispersant may be 100% by mass, that is, the dispersant is substantially composed of only the modified PVA.

[0210] The dispersant of the present application is preferably a dispersant for suspension polymerization, and may be a dispersant used when suspension polymerization of a vinyl compound.

[0211] The dispersant may be in a granular form. Alternatively, the dispersant may be dissolved in water. That is, one embodiment of the present application is an aqueous solution containing a dispersant and water.

[0212] The degree of polymerization of the modified PVA used in the dispersant of the present application is not particularly limited, and its lower limit may be, for example, 300, and is sometimes preferably 500, more preferably 600, and further preferably 650. In addition, the upper limit of the degree of polymerization may be, for example, 3000, and is sometimes preferably 1500, more preferably 1000, and further preferably 800. In addition, the viscosity-average degree of polymerization of the modified PVA is preferably 500 or more and 1500 or less. By setting the degree of polymerization of the modified PVA to the above range, when the dispersant containing the modified PVA is used as a dispersion stabilizer for suspension polymerization of a vinyl compound, the proportion of coarse particles of the obtained vinyl polymer is small, and when the obtained vinyl polymer is made into a sheet, fish eyes are reduced.

[0213] The lower limit of the saponification degree of the modified PVA used in the dispersant of the present application is also preferably 30 mol%, more preferably 60 mol%, and further preferably 80 mol%. On the other hand, the upper limit of the saponification degree of the modified PVA is also preferably 99.9 mol%, more preferably 99 mol%, further preferably 98 mol%, further preferably 93 mol%, particularly preferably 90 mol%, and more particularly preferably 85 mol%. By setting the saponification degree of the modified PVA to the above-mentioned range, the water-soluble property is improved, and the performance as the dispersant for suspension polymerization is more excellent. For example, the saponification degree of the modified PVA is preferably more than 60 mol% and less than 90 mol%. By making the saponification degree of the modified PVA the above-mentioned range, the surface active performance is more suitable for the like, thus, when the modified PVA is used as a dispersant, the vinyl polymer particles with smaller particle size can be manufactured. In addition, by making the saponification degree below the above-mentioned upper limit, the plasticizer absorbency of the vinyl polymer particles obtained by using the modified PVA as a dispersant is further improved.

[0214] The dispersant of the present application may contain various additives within the scope that does not impair the gist of the present invention. Examples of the above-mentioned additives include polymerization regulators such as aldehydes, halogenated hydrocarbons, and thiols; polymerization inhibitors such as phenol compounds, sulfur compounds, and N-oxide compounds; pH adjusters; crosslinking agents; preservatives; mildew inhibitors; anti-blocking agents; defoaming agents; compatibilizers, etc. The content of various additives in the dispersant is sometimes preferably 10% by mass or less, and more preferably 5% by mass or less relative to the total amount of the dispersant.

[0215] <Method for producing vinyl polymer>

[0216] One embodiment of the present application is a method for producing a vinyl polymer, comprising the step of subjecting a vinyl compound to suspension polymerization in the presence of the above-mentioned dispersant. In the production method, the obtained vinyl polymer may be in a granular form.

[0217] Examples of methods for adding the dispersant to the polymerization tank include (i) adding the dispersant in the form of an aqueous solution to the polymerization tank, and (ii) directly adding the dispersant in a powder state. From the viewpoint of uniformity in the polymerization tank, the method (i) is preferred.

[0218] In the suspension polymerization of the vinyl compound, the amount (concentration) of the dispersant may be 1500 ppm or less, 1000 ppm or less, or 800 ppm or less relative to the vinyl compound. The amount (concentration) of the dispersant may be 100 ppm or more, 300 ppm or more, or 500 ppm or more relative to the vinyl compound. Here, the above ppm refers to mass ppm.

[0219] Examples of vinyl compounds include halogenated vinyls such as vinyl chloride; vinyl esters such as vinyl acetate and vinyl propionate; (meth)acrylic acid, their esters and salts; maleic acid, fumaric acid, their esters and anhydrides; styrene, acrylonitrile, vinylidene chloride, vinyl ether, etc. Among them, it is preferred to use vinyl chloride alone or to use vinyl chloride and a monomer copolymerizable with vinyl chloride in combination. Examples of monomers copolymerizable with vinyl chloride include vinyl esters such as vinyl acetate and vinyl propionate; (meth)acrylic acid esters such as methyl (meth)acrylate and ethyl (meth)acrylate; α-olefins such as ethylene and propylene; unsaturated dicarboxylic acids such as maleic anhydride and itaconic acid; acrylonitrile, styrene, vinylidene chloride, vinyl ether, etc.

[0220] In the suspension polymerization of the vinyl compound, an oil-soluble or water-soluble polymerization initiator that has been used in the polymerization of the vinyl compound (e.g., vinyl chloride) can be used. Examples of the oil-soluble polymerization initiator include percarbonate compounds such as diisopropyl peroxydicarbonate, di(2-ethylhexyl) peroxydicarbonate, and diethoxyethyl peroxydicarbonate; perester compounds such as tert-butyl peroxyneodecanoate, tert-butyl peroxypivalate, tert-hexyl peroxypivalate, and cumyl peroxyneodecanoate; peroxides such as acetylcyclohexylsulfonyl peroxide, 2,4,4-trimethylpentyl-2-peroxyphenoxyacetate, 3,5,5-trimethylhexanoyl peroxide, and lauroyl peroxide; and azo compounds such as 2,2'-azobis(2,4-dimethylvaleronitrile), 2,2'-azobisisobutyronitrile, and 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile). Examples of the water-soluble polymerization initiator include potassium persulfate, ammonium persulfate, hydrogen peroxide, cumene hydroperoxide, etc. These polymerization initiators may be used alone or in combination of two or more.

[0221] When performing suspension polymerization of a vinyl compound, the polymerization temperature is not particularly limited and may be as low as about 20° C. or as high as over 90° C., preferably about 40 to 70° C. In order to improve the heat removal efficiency of the polymerization reaction system, a polymerization reactor equipped with a reflux condenser may be used.

[0222] The dispersant may be used alone in the suspension polymerization of the vinyl compound, or in combination with water-soluble cellulose ethers such as methyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, hydroxyethyl methyl cellulose (HEMC), and hydroxypropyl methyl cellulose (HPMC) within the scope not impairing the gist of the present invention; water-soluble polymers such as modified (e.g., modified based on ionic groups such as carboxylic acid and sulfonic acid) or unmodified polyvinyl alcohol, gelatin, etc. other than the above-mentioned modified PVA; oil-soluble emulsifiers such as sorbitan monolaurate, sorbitan trioleate, glyceryl tristearate, and ethylene oxide propylene oxide block copolymers; water-soluble emulsifiers such as polyoxyethylene sorbitan monolaurate, polyoxyethylene glyceryl oleate, and sodium laurate, etc.

[0223] As polyvinyl alcohols other than the above-mentioned modified PVA, for example, polyvinyl alcohol (S) having a saponification degree of less than 65 mol% and a viscosity average degree of polymerization of 50 to 750, polyvinyl alcohol (T) having a saponification degree of 65 mol% to 99.5 mol% and a viscosity average degree of polymerization of 800 to 3500, etc. can be listed. These saponification degrees and viscosity average degrees of polymerization can be measured in the same manner as the above-mentioned modified PVA. As polyvinyl alcohol (S), polyvinyl alcohol having a saponification degree of 30 to 60 mol% and a viscosity average degree of polymerization of 180 to 650 is preferred. As polyvinyl alcohol (T), polyvinyl alcohol having a saponification degree of 80 mol% to 99.5 mol% and a viscosity average degree of polymerization of 1000 to 3200 is preferred. In addition, polyvinyl alcohol (S) and polyvinyl alcohol (T) may be unmodified or modified by introducing ionic groups such as carboxylic acids and sulfonic acids to impart self-emulsification properties. The mass ratio of the modified PVA and the polyvinyl alcohol (S) used in combination (modified PVA / polyvinyl alcohol (S)) is not particularly limited, and is sometimes preferably 95 / 5 to 20 / 80, and more preferably 90 / 10 to 30 / 70. The mass ratio of the modified PVA and the polyvinyl alcohol (T) used in combination (modified PVA / polyvinyl alcohol (T)) is not particularly limited, and is sometimes preferably 95 / 5 to 20 / 80, and more preferably 90 / 10 to 30 / 70. The modified PVA and polyvinyl alcohol (S) and / or polyvinyl alcohol (T) may be added together at the initial stage of the suspension polymerization, or may be added in portions during the suspension polymerization.

[0224] The obtained vinyl polymer can be appropriately blended with a plasticizer and the like and used for various molded articles.

[0225] <Mixture>

[0226] One embodiment of the present application is a mixture comprising a vinyl compound and a dispersant. The mixture may further comprise water. The mixture may be, for example, a reaction solution comprising a vinyl compound, a dispersant and water before suspension polymerization is performed in the method for producing the vinyl polymer, or may be a reaction solution after suspension polymerization is performed. In addition, one embodiment of the present application is a mixture comprising a vinyl polymer and a dispersant. The mixture may further comprise water. The mixture may be, for example, a reaction solution after suspension polymerization is performed in the method for producing the vinyl polymer.

[0227] The present invention includes various combinations of the above-described configurations within the technical scope of the present application as long as the effects of the present invention are exhibited.

[0228] Example

[0229] Hereinafter, the present application will be described in more detail using Examples. Hereinafter, "parts" and "%" are by mass unless otherwise specified.

[0230] [Saponification degree of PVA]

[0231] The saponification degree (mol %) of PVA (raw material PVA or modified PVA) is determined by the method described in JIS-K6726-1994.

[0232] [Viscosity of 4 mass % aqueous solution of raw material PVA]

[0233] In a water bath at room temperature, prepare a 300mL flask equipped with a stirrer and a reflux condenser, put in 192g of distilled water, and start stirring at 300rpm. Weigh 8g of PVA and slowly put it into the flask. After the total amount of PVA (8g) is put in, it takes about 30 minutes to raise the temperature of the water bath to 95°C. After the internal temperature of the flask reaches 90°C, it continues to dissolve while stirring at 300rpm for 2 hours, and then the temperature of the water bath is set to room temperature, while slowly stirring the flask while cooling. The resulting aqueous solution is transferred to a 100mL sample tube, and the viscosity at a rotation speed of 60rpm is measured at 20°C using a B-type viscometer BLII (manufactured by Toki Sangyo Co., Ltd.).

[0234] [Viscosity average degree of polymerization]

[0235] The viscosity average degree of polymerization of the raw material PVA or the modified PVA is measured in accordance with JIS-K6726-1994.

[0236] [Modification amount of the functional group derived from the silane coupling agent in the modified PVA (content of the structural unit represented by the above formula (1))]

[0237] The modified amount of the functional group derived from the silane coupling agent in the modified PVA (the content of the structural unit represented by the above formula (1): mol %) was determined as follows: 1 It was determined by the H-NMR method.

[0238] [Dispersion Degree A of Silicon Atoms in Modified PVA Particles]

[0239] Regarding the dispersion degree A of silicon atoms in the modified PVA particles, 10 approximately spherical particles with a particle size of more than 100 μm were selected, and these particles were divided into two equal parts in a manner to maximize the cross-sectional area. The center of the inscribed circle of the cross section was taken as the center of the particle, and the point of intersection between the inscribed circle and the surface of the particle was taken as the particle surface. The silicon atom content was measured using an energy dispersive X-ray analyzer (EDS) as described above, and the dispersion degree A was calculated according to the following formula.

[0240] Dispersion A = Silicon atom content in the center of the particle (mol %) / Silicon atom content on the surface of the particle (mol %)

[0241] After embedding a modified PVA particle with a thermosetting epoxy resin, a Curatron UC7 / FC7 (manufactured by Lionmac Systems) was used to cut the particle in a frozen state to expose the particle cross section as an observation sample. In order to perform charge correction on the observation sample, platinum evaporation was performed with a thickness of about 2nm using MC1000 manufactured by Hitachi Hitech. Next, a scanning electron microscope (SEM) SU-70 (manufactured by Hitachi Hitech) was used to take a cross-sectional image of the polyvinyl alcohol resin, and an energy dispersive X-ray analyzer (EDS, X-Max50 manufactured by Technosoft Instruments) was used to perform elemental analysis at the end and center of the particle. Image observation / elemental analysis was performed under ultra-high vacuum. EDS analysis was performed on a secondary electron image obtained at an observation magnification of 2500 times, an acceleration voltage of 15 kV, and a working distance of 15 mm, and the elemental composition was obtained from the obtained spectrum. The average value of 10 measurement samples was set as the silicon atom content.

[0242] [Water-insoluble components of modified PVA]

[0243] In a water bath set to 20°C, a 500mL flask equipped with a stirrer and a reflux condenser was added to the flask. 285g of distilled water was added to the flask and stirring was started at 300rpm. 15g of modified PVA particles were weighed and slowly added to the flask. After the total amount of modified PVA particles (15g) was added, it took 30 minutes to raise the temperature of the water bath to 90°C, thereby dissolving the modified PVA particles and obtaining a modified PVA solution. After the temperature of the water bath reached 90°C, the solution was further dissolved while stirring at 300rpm for 60 minutes. Thereafter, the modified PVA solution was used to filter the undissolved and residual modified PVA particles (insoluble particles) with a metal filter with a mesh of 63μm. Next, the filter was thoroughly cleaned with 90°C warm water to remove the modified PVA solution attached to the filter, leaving only the insoluble particles on the filter, and then the filter was dried with a 120°C heating dryer for 1 hour. The mass of the filter after drying was compared with the mass of the filter before filtration to calculate the mass of the insoluble particles. The ratio of the mass of the insoluble particles to the mass of the modified PVA initially added to the water (15 g) was defined as the water-insoluble content (ppm).

[0244] [Example 1]

[0245] 3.0 parts of vinyltrimethoxysilane as a silane coupling agent, 0.13 parts of acetic acid as a catalyst and 7.0 parts of methanol as a solvent were added to a 100 mL beaker to prepare a methanol solution of vinyltrimethoxysilane. Next, 100 parts of PVA particles having a 4 mass % aqueous solution viscosity of 5 mPa·s and a saponification degree of 88 mol % were added to a 1 L wide-mouthed eggplant flask, where the methanol solution of the above-mentioned vinyltrimethoxysilane was sprayed and impregnated to obtain a mixture of vinyltrimethoxysilane and PVA. The eggplant flask was stored (heat treated) in a hot air dryer at 80°C for 4 hours to obtain a granular modified PVA (1) in which vinyltrimethoxysilane reacted. The obtained modified PVA (1) had a saponification degree of 88 mol %, a modification amount of 0.4 mol %, a dispersion A of 0.98, and a water-insoluble component of less than 10 ppm, and excellent water solubility. The obtained modified PVA (1) was in a granular form and had excellent water solubility, and therefore, it was found that it had excellent handling properties.

[0246] [Examples 2 to 9, Comparative Examples 1 to 2]

[0247] Modified PVA (2) to (11) were produced in the same manner as in Example 1 except that the type of raw material PVA used, the type and amount of solvent, the type and amount of silane coupling agent, the type and amount of catalyst, and the production conditions (heat treatment conditions) were changed as shown in Table 1. The evaluation results of the dispersion degree A, saponification degree, modification amount, and water-insoluble content of each modified PVA obtained are shown in Table 2.

[0248] [Table 1]

[0249]

[0250] [Table 2]

[0251]

[0252] As shown in Table 2, the water-insoluble components of the modified PVA (1) to (9) of the examples are less than 1000 ppm and have excellent water solubility. Although this modified PVA has functional groups derived from silane coupling agents, it still has excellent water solubility, and therefore has excellent handling properties and can be used in a variety of applications. On the other hand, as in Comparative Example 1, the modified PVA (10) obtained by reacting PVA with a silane coupling agent under alkaline conditions may have excessive cross-linking of the silane coupling agent, so the water-insoluble components exceed 1000 ppm and have poor water solubility. This modified PVA has poor handling properties and is difficult to use in a variety of applications. In addition, as in Comparative Example 2, when hexane is used as a solvent in the impregnation process, the silane coupling agent may not be well penetrated into the PVA because the PVA does not swell, so the dispersion degree A of the particles of the obtained modified PVA (11) is low and the water-insoluble components are high. The water solubility and handling properties of the modified PVA (11) are also poor.

[0253] [Example 10]

[0254] In a 100 ml beaker, 4.8 parts of vinyltrimethoxysilane (silane coupling agent) and 0.13 parts of acetic acid were added to 11.2 parts of methyl acetate to prepare a methyl acetate solution of vinyltrimethoxysilane. Next, 100 parts of PVA (raw material PVA) having a viscosity-average polymerization degree of 1000, a 4 mass % aqueous solution viscosity of 10 mPa·s, and a saponification degree of 94 mol % were added to a 1 L wide-mouthed eggplant-shaped flask, where the solution was sprayed and impregnated to obtain a mixture of vinyltrimethoxysilane and PVA. The eggplant-shaped flask was stored (heat treated) in a hot air dryer at 80° C. for 4 hours to obtain a modified PVA (12) in which the raw material PVA and vinyltrimethoxysilane reacted. The obtained modified PVA (12) had a viscosity average degree of polymerization of 1000, a saponification degree of 94 mol %, a modification amount of vinyltrimethoxysilane of 0.55 mol %, a dispersion degree A of 0.87, and a water-insoluble component of 60 ppm.

[0255] [Examples 11 to 17, Comparative Example 3]

[0256] Except that the type of raw material PVA used, the type and amount of solvent, the type and amount of silane coupling agent, the type and amount of catalyst, and the manufacturing conditions (heat treatment conditions) were changed as shown in Table 3, the same operation as in Example 10 was carried out to manufacture modified PVA (13) to (19) and PVA (X), and their physical properties were evaluated. The results are shown in Table 4.

[0257] [Production of release paper base]

[0258] Using the modified PVAs (12) to (19) and PVA (X) obtained in Examples 10 to 17 and Comparative Example 3, base papers for release papers were prepared by the following method and evaluated.

[0259] A 6 mass % aqueous solution of modified PVA was prepared as a coating liquid. The coating liquid was applied in an amount of about 2.0 g / m2 in terms of dry mass using a wire bar. 2 The coated paper was coated on a glass paper with an air permeability resistance of 100 seconds. After coating, the coated paper was dried at 100°C for 5 minutes. The coated paper was polished using a super calender at 70°C and 400 kg / cm 2 The obtained coated paper was treated twice to obtain a base paper for release paper having a coating layer derived from the coating liquid, that is, a silicone plugging layer.

[0260] [Evaluation of air resistance of release paper base paper]

[0261] The air resistance of the release paper base paper was measured using a Wangyan air permeability tester in accordance with JIS-P8117-2009, and the air resistance was used as an indicator of the packing property of the silicone in the release paper base paper. There is a tendency that the higher the air resistance, the better the packing property of the silicone. The results are shown in Table 4.

[0262] [Evaluation of silicone curability]

[0263] As addition silicone, LTC1056L manufactured by Toray Daw Coning Co., Ltd. was used, and as platinum catalyst, SRX212 was used, and the addition silicone and platinum were mixed in a mass ratio of 100 / 0.007 to prepare a solution. The obtained solution was coated with a blade coater at a solid content of 2.0 g / m 2The silicone filling layer of the obtained release paper base paper was coated in a manner. Thus, a silicone layer was formed on the release paper base paper. Furthermore, a heat treatment was performed at 110°C, and the time until the silicone solidified was measured. Here, the time until the silicone solidified refers to the time (seconds) required for the silicone layer to completely stop peeling off after the silicone layer was strongly rubbed 10 times with fingers at a prescribed time interval. The results are shown in Table 4.

[0264] [Evaluation of Adhesion of Peel Layer]

[0265] As addition silicone, LTC1056L manufactured by Toray Daw Coning Co., Ltd. was used, and as platinum catalyst, SRX212 was used, and the addition silicone and platinum were mixed in a ratio of 100 / 0.009 to prepare a solution. The obtained solution was coated with a blade coater at a solid content of 2.0 g / m 2 The obtained release paper was coated on the silicone filling layer on the release paper base paper in a manner of 100° C., and heat treated at 110° C. for 90 seconds to obtain a release paper having a release layer (silicone layer) formed on the release paper base paper. The obtained release paper was evaluated according to the following indicators. The results are shown in Table 4.

[0266] A + : After leaving it at 40°C and 90% RH for one week, the peeling layer was strongly rubbed with fingers. As a result, the peeling layer did not peel off. After leaving it at the same condition for another week, the peeling layer was strongly rubbed with fingers. As a result, the peeling layer did not peel off.

[0267] A: After leaving it at 40°C and 90% RH for one week, the peeling layer was strongly rubbed with fingers. As a result, the peeling layer did not peel off. However, after leaving it at the same condition for another week, the peeling layer was strongly rubbed with fingers, and the peeling layer peeled off.

[0268] B: After being left to stand at 40°C and 90% RH for one week, the release layer was strongly rubbed with fingers. As a result, the release layer was peeled off.

[0269] C: After being left to stand at 40° C. and 90% RH for one week, the release layer was lightly rubbed with a finger. As a result, the release layer was peeled off.

[0270] [Table 3]

[0271]

[0272] [Table 4]

[0273]

[0274] As shown in Table 4, the silicones of Examples 10 to 17 were excellent in curability and adhesion, whereas the silicone of Comparative Example 3 was poor in curability and adhesion. In addition, Examples 13 and 14 also had high air permeability resistance (clogging properties).

[0275] [Example 18]

[0276] In a 100 mL beaker, 4.0 parts of vinyltrimethoxysilane (silane coupling agent) and 0.11 parts of acetic acid were added to 9.3 parts of methyl acetate to prepare a methyl acetate solution of vinyltrimethoxysilane. Next, 100 parts of PVA (raw material PVA) having a viscosity-average polymerization degree of 750, a 4 mass % aqueous solution viscosity of 8 mPa·s, and a saponification degree of 72 mol % were added to a 1 L wide-mouthed eggplant-shaped flask, where the above solution was sprayed and impregnated to obtain a mixture of vinyltrimethoxysilane and PVA. The eggplant-shaped flask was stored (heat treated) in a hot air dryer at 80° C. for 4 hours to obtain a modified PVA (20) in which the raw material PVA and vinyltrimethoxysilane reacted. The obtained modified PVA (20) had a viscosity average degree of polymerization of 750, a saponification degree of 72 mol %, a modification amount of vinyltrimethoxysilane of 0.5 mol %, a dispersion degree A of 0.98, and a water-insoluble component of less than 10 ppm.

[0277] [Examples 19 to 24, Comparative Example 4]

[0278] Except that the type of raw material PVA used, the type and amount of solvent, the type and amount of silane coupling agent, the type and amount of catalyst, and the manufacturing conditions (heat treatment conditions) were changed as shown in Table 5, the same operation as in Example 18 was carried out to manufacture modified PVA (21) to (26) and PVA (Y), and their physical properties were evaluated. The results are shown in Table 6.

[0279] [Evaluation of vinyl polymers]

[0280] Using the modified PVAs (20) to (26) obtained in Examples 18 to 24 and the PVA (Y) obtained in Comparative Example 4 as dispersants for suspension polymerization, particles of polyvinyl chloride as a vinyl polymer were obtained by the following method.

[0281] 1390 g of an aqueous solution in which 0.94 g of each dispersant for suspension polymerization (1000 ppm relative to vinyl chloride monomer) is dissolved is placed in a 5 L autoclave. Next, 1.5 g of a 70% toluene solution of diisopropyl peroxydicarbonate is placed in the autoclave. Degas until the pressure in the autoclave reaches 0.0067 MPa to remove oxygen. Thereafter, 940 g of vinyl chloride is added, the temperature of the contents in the autoclave is raised to 57°C, and suspension polymerization is started under stirring. The pressure in the autoclave at the start of the polymerization is 0.83 MPa. After 4 hours from the start of the suspension polymerization, the polymerization is stopped when the pressure in the autoclave reaches 0.65 MPa, and the unreacted vinyl chloride is removed. Thereafter, the polymerization slurry is taken out and dried at 65°C overnight to obtain vinyl chloride polymer particles.

[0282] The average particle size (MGS), the amount of coarse particles, and fisheyes of the obtained vinyl chloride polymer particles (vinyl polymer particles) were evaluated by the following methods.

[0283] [Evaluation method]

[0284] (1) Average particle size (μm)

[0285] The particle size distribution was measured by the dry sieving method described in JIS-Z8815-1994 using a JIS standard sieve, and the results were plotted on a Rosin-Rammler distribution to calculate the average particle size (dp50).

[0286] (2) Amount of coarse particles (%)

[0287] The content (mass %) of the vinyl chloride polymer particles that did not pass through a sieve with a mesh size of 355 μm (42 meshes according to the JIS standard sieve mesh conversion) was evaluated according to the following evaluation criteria. The above content refers to the accumulation (%) on the sieve. The mesh size of the sieve is based on the nominal mesh size W of JIS-Z8801-1-2006.

[0288] A + : Less than 0.5% by mass

[0289] A: 0.5 mass % or more and less than 1.0 mass %

[0290] B: 1.0 mass% or more and less than 2.5 mass%

[0291] C: 2.5 mass % or more

[0292] (3) Fisheye (pieces)

[0293] 100 parts of vinyl chloride polymer pellets, 50 parts of dioctyl phthalate, 5 parts of tribasic lead sulfate and 1 part of lead stearate were roll-kneaded at 150°C for 7 minutes to prepare 5 sheets with a thickness of 0.1 mm and a size of 1400 mm x 1400 mm. The number of fish eyes was visually measured. 2 The number of fisheyes is evaluated according to the following criteria. The fewer the number of fisheyes, the fewer defects on the chip.

[0294] A + :0~5

[0295] A: 6 to 10

[0296] B: 11 to 49

[0297] C: 50 or more

[0298] [Table 5]

[0299]

[0300] [Table 6]

[0301]

[0302] As shown in Table 6, when the modified PVA (20) to (26) of Examples 18 to 24 were used as dispersants, the average particle size of the obtained vinyl polymer particles was small, and a high-quality vinyl chloride polymer resin with a small number of coarse particles and fish eyes could be obtained.

[0303] Industrial Applicability

[0304] Although the modified PVA of the present application has a functional group derived from a silane coupling agent, it still has excellent water solubility and high handleability. Therefore, the modified PVA of the present application can be used in various applications such as dispersants, covering agents, adhesives, and binders, and has a very high industrial utilization value.

Claims

1. A modified vinyl alcohol polymer having a structural unit represented by the following formula (1), wherein the content of the structural unit represented by the above formula (1) is 90 mol% or more relative to all structural units containing silicon atoms, and the water-insoluble component is 1000 ppm or less, [Chemistry 1] In formula (1), X, Y and Z are each independently an alkyl group having 1 to 20 carbon atoms, an alkenyl group having 2 to 20 carbon atoms, a phenyl group, a benzyl group, a vinylphenyl group, a haloalkyl group having 1 to 20 carbon atoms, a halophenyl group, an aminoalkyl group having 1 to 20 carbon atoms, a mercaptoalkyl group having 1 to 20 carbon atoms, a ureidoalkyl group having 2 to 20 carbon atoms, an isocyanatealkyl group having 2 to 8 carbon atoms, a group having 3 to 20 carbon atoms including an epoxy group, a group having 3 to 20 carbon atoms including an acrylamide group, a group having 4 to 20 carbon atoms including a methacrylamide group, an acetoxy group or -(CH2) n -OR 1 The group shown, wherein R 1 represents a hydrogen atom, an alkali metal atom, an alkaline earth metal atom, an alkyl group having 1 to 20 carbon atoms, an alkenyl group having 2 to 20 carbon atoms, an acryloyl group, a methacryloyl group or a glycidyl group, and n represents an integer of 0 to 6.

2. The modified vinyl alcohol polymer according to claim 1, wherein The content of the structural unit represented by the above formula (1) is 0.01 mol% or more and less than 5 mol%. 3 . The method for producing a modified vinyl alcohol polymer according to claim 1 , comprising the step of impregnating a solid vinyl alcohol polymer with a silane coupling agent.

4. The method for producing a modified vinyl alcohol polymer according to claim 3, wherein In the impregnation step, the solution containing the silane coupling agent is sprayed onto the vinyl alcohol polymer particles to impregnate them.

5. The method for producing a modified vinyl alcohol polymer according to claim 3, wherein The silane coupling agent has a structure represented by the following formula (2): In formula (2), R is an alkyl group having 1 to 8 carbon atoms, an acetyl group or -(CH2) m -OR 2 , where R 2 represents an alkyl group having 1 to 20 carbon atoms, m represents an integer of 1 to 6; X, Y and Z are each independently an alkyl group having 1 to 20 carbon atoms, an alkenyl group having 2 to 20 carbon atoms, a phenyl group, a benzyl group, a vinylphenyl group, a haloalkyl group having 1 to 20 carbon atoms, a halophenyl group, an aminoalkyl group having 1 to 20 carbon atoms, a mercaptoalkyl group having 1 to 20 carbon atoms, a ureidoalkyl group having 2 to 20 carbon atoms, an isocyanatealkyl group having 2 to 8 carbon atoms, a group having 3 to 20 carbon atoms including an epoxy group, a group having 3 to 20 carbon atoms including an acrylamide group, a group having 4 to 20 carbon atoms including a methacrylamide group, an acetoxy group or -(CH2) n -OR 1 The group shown, wherein R 1 represents an alkyl group having 1 to 20 carbon atoms, an alkenyl group having 2 to 20 carbon atoms, an acryloyl group, a methacryloyl group or a glycidyl group, and n represents an integer of 0 to 6. 6 . The method for producing a modified vinyl alcohol polymer according to claim 3 , further comprising: a step of heat-treating the vinyl alcohol polymer impregnated with the silane coupling agent obtained in the impregnation step.

7. Particles comprising the modified vinyl alcohol polymer according to claim 1 or 2.

8. The particle according to claim 7, wherein The dispersion degree A of silicon atoms is 0.2 or more and less than 1.

9. An aqueous solution comprising the modified vinyl alcohol polymer according to claim 1 or 2.

10. A coating liquid comprising a modified vinyl alcohol polymer having a structural unit represented by the following formula (1), wherein the content of the structural unit represented by the above formula (1) relative to all structural units containing silicon atoms is 90 mol% or more, and the water-insoluble component of the above modified vinyl alcohol polymer is 1000 ppm or less. [Chemistry 3] In formula (1), X, Y and Z are each independently an alkyl group having 1 to 20 carbon atoms, an alkenyl group having 2 to 20 carbon atoms, a phenyl group, a benzyl group, a vinylphenyl group, a haloalkyl group having 1 to 20 carbon atoms, a halophenyl group, an aminoalkyl group having 1 to 20 carbon atoms, a mercaptoalkyl group having 1 to 20 carbon atoms, a ureidoalkyl group having 2 to 20 carbon atoms, an isocyanatealkyl group having 2 to 8 carbon atoms, a group having 3 to 20 carbon atoms including an epoxy group, a group having 3 to 20 carbon atoms including an acrylamide group, a group having 4 to 20 carbon atoms including a methacrylamide group, an acetoxy group or -(CH2) n -OR 1 The group shown, wherein R 1 represents a hydrogen atom, an alkali metal atom, an alkaline earth metal atom, an alkyl group having 1 to 20 carbon atoms, an alkenyl group having 2 to 20 carbon atoms, an acryloyl group, a methacryloyl group or a glycidyl group, and n represents an integer of 0 to 6.

11. The coating liquid according to claim 10, wherein The content of the structural unit represented by the formula (1) in the modified vinyl alcohol polymer is 0.01 mol% or more and less than 5 mol%.

12. The coating liquid according to claim 10 or 11, wherein The modified vinyl alcohol polymer has a viscosity average degree of polymerization of 500 to 5000, and a saponification degree of 70 mol % to 99.9 mol %.

13. A coated article, which is obtained by applying the coating liquid according to any one of claims 10 to 12 onto a substrate.

14. A dispersant comprising a modified vinyl alcohol polymer having a structural unit represented by the following formula (1), wherein the content of the structural unit represented by the above formula (1) in the above modified vinyl alcohol polymer is 90 mol% or more relative to all structural units containing silicon atoms, and the water-insoluble component of the above modified vinyl alcohol polymer is 1000 ppm or less. [Chemistry 4] In formula (1), X, Y and Z are each independently an alkyl group having 1 to 20 carbon atoms, an alkenyl group having 2 to 20 carbon atoms, a phenyl group, a benzyl group, a vinylphenyl group, a haloalkyl group having 1 to 20 carbon atoms, a halophenyl group, an aminoalkyl group having 1 to 20 carbon atoms, a mercaptoalkyl group having 1 to 20 carbon atoms, a ureidoalkyl group having 2 to 20 carbon atoms, an isocyanatealkyl group having 2 to 8 carbon atoms, a group having 3 to 20 carbon atoms including an epoxy group, a group having 3 to 20 carbon atoms including an acrylamide group, a group having 4 to 20 carbon atoms including a methacrylamide group, an acetoxy group or -(CH2) n -OR 1 The group shown, wherein R 1 represents a hydrogen atom, an alkali metal atom, an alkaline earth metal atom, an alkyl group having 1 to 20 carbon atoms, an alkenyl group having 2 to 20 carbon atoms, an acryloyl group, a methacryloyl group or a glycidyl group, and n represents an integer of 0 to 6.

15. The dispersant according to claim 14, wherein The content of the structural unit represented by the formula (1) in the modified vinyl alcohol polymer is 0.01 mol% or more and less than 5 mol%.

16. The dispersant according to claim 14 or 15, wherein The modified vinyl alcohol polymer has a viscosity average degree of polymerization of 500 to 1500, and a saponification degree of 60 mol % to 90 mol %.

17. The dispersant according to claim 14 or 15, which is used for suspension polymerization. 18 . A method for producing a vinyl polymer, comprising: a step of subjecting a vinyl compound to suspension polymerization in the presence of the dispersant according to claim 14 .

19. A mixture comprising a vinyl compound and the dispersant according to any one of claims 14 to 17.

Citation Information

Patent Citations

  • Water-soluble silane-modified polyvinyl alcohol

    JP1991119002A

  • Resin composition

    JP2002275338A

  • Stock paper of releasing paper

    JP2005194672A

  • Cellulose fiber-based support containing a modified PVA layer, and method for manufacturing and using the same.

    JP2013531136A

  • Dispersion stabilizer

    WO2007119735A1